Stathmin-mediated autophagy drives the differentiation of dermal fibroblast into myofibroblast under TGFβ1 stimulation - Hui Tang; Luqi Yang; Yanhai Feng; Jianxin Wu; Yi Liang; Zhenglin Li; Lingbo Li; Wan Zhao; Xiaolin Deng; Dan Luo; Xia Lei; Lingfei Li (Molecular Biology Reports, 2026)

Long-term organic fertilization fosters modular microbial networks: A global analysis of soil bacteriome responses - Shu-Le Li; Cai Chen; Xiang-Yu Dai; Hai-Song Yan; Yao-Yang Xu; Meili Feng; Jun He; Jianfeng Ren; Wan-Ying Xie; Fang-Jie Zhao (Soil Ecology Letters, 2026)

Accelerating large-scale plane-wave hybrid functional calculations via low-rank approximations and high-performance computing on the Sugon supercomputer - Yufan Yao; Junwei Feng; Lingyun Wan; Shizhe Jiao; Jielan Li; Junshi Chen; Hong An; Xinming Qin; Wei Hu; Jinlong Yang (Computer Physics Communications, 2026)

Chloride reinforces nanowire electrocatalytic peracetic acid filtration for inactivating oxidant-resistant bacteria: A sequential PAA reduction and chloride oxidation pathway - Cong-Cong Feng; Wan-Bin Li; Hai Liu (Water Research, 2026)

Size matching between laccase and carrier via tunable diamine-derived flexible spacer arms for enhanced phenolic wastewater degradation - Jie Zhang; Yiqi Gong; Zhipeng Qin; Xinyi Liu; Jiao Yu; Tao Feng; Wan Zhang; Wenjing Lin; Kaiyue Kang; Xuemei Tan; Lin Zhuo; Ruiqi Wang; et al. (Journal of Water Process Engineering, 2026)

Al-modified ReS2/TiO2 with enhanced adsorption and stepwise interfacial charge migration for photocatalytic PFOA removal - Ran Chen; Feng Liu; Zhenkai Liu; Jun Wan; Qidi Liu; Yixin Ma; Yan Li; Shunli Wan; Yongming Luo; Haijiao Xie (Journal of Environmental Chemical Engineering, 2026)

Progress in modification strategies of perovskite oxides for CO2 electrolysis in solid oxide electrolysis cells - Yuanxin Xie; Teng Li; Ruoping Li; Jing Ding; Nengjie Feng; Xuebin Luan; Gongde Wu; Wei Du; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2026)

Association of real-time noise exposure with rest-activity circadian rhythms and sleep health: a 7-day longitudinal measure among Hong Kong nurses with night-shifts - Xueqiong Weng; Natalie H.Y. Tang; Julie Y.T. Ma; Cherry C.M. Wan; Yufei Liu; Feng Wang; Beixi Li; Gengze Liao; Wenzhen Li; Amy Wing-Yin Ho; Chung Shun Ho; Victoria H. Arrandale; et al. (Environmental Pollution, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Advanced nitrogen removal system coupling partial nitritation, anammox, denitrification and oxygen-permeable hollow-fibre membranes for precise oxygen regulation - Xifang Tang; Bao-Shan Xing; Yong-Ning Feng; Liguo Wan; Ling-Hu Li; Xin-Xin Sun; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

A cell surface-targeted MNAzyme-aptamer system for highly sensitive and visual detection of cancer cells via nucleolin activation - Yingjie Chen; Lu Tang; Kai Feng; Jiahui Xiang; Yao Liu; Tao Wan; Dairong Li (Analytica Chimica Acta, 2026)

Long-day photoperiod promotes growth of pea (Pisum sativum L.) via auxin biosynthesis and polar transport - Luping Gu; Tao Wan; Wenjie Chen; Guiyu Zhou; Huiyu Zhang; Chang Tan; Lars H. Wegner; Sergey Shabala; Xuewen Li; Jiayou Liu; Yingming Feng; Renfang Shen; et al. (Plant Science, 2026)

Quantitative assessment of fluoride enrichment mechanisms and consequent health risks in geothermal waters of the Yishu Fault Zone using hydrochemical and multi-isotopic (H, O, Sr, S) tracers - Luyao Wang; Kai Liu; Shouchuan Zhang; Li Wan; Fangyuan Jiang; Hui Feng; Yaoyao Zhang; Longqiang Zhang; Jialiang Wang (Geothermics, 2026)

Decoding the honey-like aroma formation in Chinese rice-flavor baijiu via key aroma compounds and their perceptual interaction - Peiqi Li; Kaijun Xie; Yufeng Feng; Qiang Li; Long Zhang; Ruijie Wan; Zhenzhen Ning; Yuchan Wei; Hehe Li; Shuang Chen; Yan Xu (Food Research International, 2026)

Sedimentary records of silicate weathering on the continental shelf of the South Yellow Sea during glacial periods - Jin Zhang; Shiming Wan; Yifei Yang; Shouye Yang; Peter D. Clift; Yulong Guo; Debo Zhao; Yi Tang; Zhaojie Yu; Zehua Song; Zhongjing Cheng; Zaibao Yang; et al. (Science China Earth Sciences, 2026)

Maize/peanut intercropping alleviates continuous peanut cropping stress via root exudate– and rhizosphere bacteria–mediated mechanisms - Zizheng Li; Li Cui; Jie Zhang; Tingting Yi; Hong Yu; Jialei Zhang; Sha Yang; Nianyuan Jiao; Feng Guo; Shubo Wan (Soil and Tillage Research, 2026)

Deep learning-based microfluidic rapid phenotypic AST uncovers early resistance trajectories - Shunji Li; Chenxi Dai; Dongjuan Chen; Chao Wan; Wenhui Wang; Xin Wang; Jingxuan Liu; Ying Zhang; Jinyi Xu; Wei Du; Xiaojun Feng; Yiwei Li; et al. (Science Bulletin, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Recovery time patterns of vegetation productivity following anomalies preceding abrupt declines - Maohong Wei; Hailing Li; Xuhao Wan; Lin Zhu; Weiqing Meng; Jianfeng Feng (Journal of Environmental Management, 2026)

Charge-shielding assembly enables biointerface engineering of polyhexamethylene biguanide for selective and resistance-resilient antibacterial therapy - Xinyun Zeng; Min Wang; Pan Mao; Lei Zhang; Yongyi Yao; Ziqi Yin; Peiren Chen; Lei Wan; Wei Su; Xia Li; Xin Li; Pei Tang; et al. (Chemical Engineering Journal, 2026)

Eco-friendly aqueous synthesis of multifunctional zero-dimensional rare-earth pseudohalide hybrids for mechanoluminescence, optical thermometry, and X-ray scintillation - Feng Liu; Jun Wan; Lu Yu; Guanfeng Ji; Riming Hu; Pifu Gong; Xiaojia Wang; Yuhai Zhang; Hongbo Wang; Jinkai Li; Haiqing Wang; Mei Yan; et al. (Chemical Engineering Journal, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Real-time, depth-resolved permafrost thermal monitoring across the Qinghai-Tibet Plateau enabled by bayesian-optimized deep learning - Xixian Kang; Zhongxia Li; Junwei Wan; Haibo Feng; Chong Ma; Xianshuo Yang (Climate Dynamics, 2026)

Investigating the propagation time and influencing factors from meteorological drought to agricultural drought in the Qinghai-Tibetan Plateau - Ning Yuan; Wensheng Wang; Sihai Liang; Xiaojun Wang; Hanxu Liang; Tao Yin; Yuqing Feng; Guangjun Wang; Li Wan (Advances in Space Research, 2026)

Microplankton three-dimensional dispersal pattern in strait: A case of ciliate community connectivity driven by the Kuroshio Current and deep overflow in the Luzon Strait - Mengxuan Chi; Feng Zhao; Shuaiyan Wang; Tingting Yin; Lihan Wang; Longzhao Li; Yuanyuan Wan; Dan Zhu; Kuidong Xu (Regional Studies in Marine Science, 2026)

Climate-change-driven planted forest growth decline especially after 2010 on the Loess Plateau - Liu Jinhao; Zhao Zhengyuan; Wan Lingfan; Liu Yaling; Li Zongshan; Feng Xiaoming (Forest Ecology and Management, 2026)

Ultrastable Pt clusters confined on CeO2 nano-islands for efficient low-temperature propane dehydrogenation over carbon nanotube - Jian Tao; Shu-Lin Liu; Zi-Dan Li; Wan-Yi Wang; Chuan-Feng Huang; Bao-Lian Su; Zhao Wang (Chemical Engineering Journal, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Phytochemical and biological studies on rare and endangered plants endemic to China. Part XLIX. Terpenoids and phenylpropanoid-substituted flavan-3-ols from the leaves of Camellia petelotii (golden-flower tea) and their bioactivities - Ze-Yu Zhao; Can Wang; Zhe-Lu Jiang; Jiang Wan; Juan Xiong; Yi Zang; Yeun-Mun Choo; Jia Li; Jin-Feng Hu (Phytochemistry, 2026)

Pilot-scale study of hollow fiber nanofiltration membranes for tap water treatment: Effects of organics on filtration performance - Yiran Li; Xuejun Bi; Yuan Gao; Chentongguang Yu; Wanhe Wan; Yanfen Chen; Yue Ma; Shujuan Huang; Jianyong Feng (Journal of Environmental Chemical Engineering, 2026)

Structure–function relationships in chitosan films containing ZIF-8-confined Ligusticum jeholense essential oil: pH-triggered release and apple ring rot control - Xiao-Yi Tong; Yun-Feng Liu; Zhi-Hong Xu; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An; Fei Cao (Food Chemistry, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Regulation of Cadmium Uptake and Agronomic Traits in Rice by PEI-Induced Nanosilica Deposition - Xiao Tian; Yingming Feng; Xingyun Chen; Tao Wan; Chaozheng Huang; Xuewen Li; Sergey Shabala; Min Yu (Journal of Soil Science and Plant Nutrition, 2026)

Dietary creatine supplementation promoted growth performance, muscle growth and protein deposition in red swamp crayfish (Procambarus clarkii) fed with all-plant-protein diets - Xinyuan Li; Changchun Song; Shouqi Xie; Min Wan; Yangyang Liu; Chenxi Wang; Guogen Su; Feng Huang; Juan Tian (Aquaculture, 2026)

Plastic film mulch mitigates soil respiration by reducing the duration of freeze-thaw transition - Yufei Li; Kaiping Zhang; Wucheng Zhao; Yuling Li; Ningning Zhang; Pingxing Wan; Zhongke Zhou; Jianjun Yang; Hongyuan Kan; Feng Zhang (Soil and Tillage Research, 2026)

Dynamic dose–time proteomic profiling of cadmium exposure in rat prefrontal cortex - Zhijian Hu; Feng Han; Hao Gao; Sheng Wan; Hui Liu; Li Jie; Yinghui Yin; Maoqin Tian; Yong Yang; Wenjie Chen; Xiao Tan; Xinxin Shi; et al. (NeuroToxicology, 2026)

Precise and high-throughput origin discrimination for green coffee beans by mass spectrometry-based metabolic analysis - Zifan Yang; Yuchen Feng; Zihang Yang; Ziqi Luo; Weikang Shu; Yanhui Wang; Bin Li; Ziheng Qi; Jingjing Wan (Food Research International, 2026)

Deficiency of primate-specific TFDP3 causes male infertility with oligoasthenoteratozoospermia in humans and cynomolgus monkeys - Chunyu Liu; Chaofeng Tu; Peng Li; Huan Wu; Feng Wan; Yong Lu; Shuyan Tang; Xin Li; Kuokuo Li; Jiaxiong Wang; Yang Gao; Xinyan Geng; et al. (Science China Life Sciences, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Observation of Concurrent Latitudinal and Longitudinal Fractionations of α- and β-HCH in Chinese Rural Surface Soil: Implications for Global Lifecycle - Shuai Hao; Yi-Fan Li; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Wen-Long Li; Ning-Zheng Zhu; Pu-Fei Yang; Hong-Liang Jia; Min-Gang Cai; Roland Kallenborn; Derek CG Muir (Archives of Environmental Contamination and Toxicology, 2026)

Decoding the core microbiota during liquor fermentation of sauce-aroma baijiu: Advances in the characteristics of core microbial communities and their regulatory strategies - Cheng Wu; Xiuting Li; Bo Wan; Feng Hu; Jianfeng Hu; Hu Lu; Xi Chen; Weiwei Li; Diqiang Wang; Baoguo Sun (Food Research International, 2026)

Evaluation of near infrared spectroscopy for direct detection of common microplastics contamination in camel Milk powder - Chunxu WAN; Yin LIU; Jing XIE; Feng CHEN; Huijie SHEN; Rong LI (Food Chemistry, 2026)

Chromosomal Fusions Promote Speciation in Subterranean Blind Mole Rats - Zhuoran Kuang; Xiaojie Yang; Zachariah Gompert; Qijiao Duan; Wenyu Liu; Sanyuan Liu; Jiaqi Chen; Xiaolong Liang; Leyan Mao; Na Wan; Yinjia Wang; Zhilong Feng; et al. (Molecular Ecology, 2026)
The genomic mechanisms underlying large‐scale chromosomal rearrangements and their evolutionary consequences remain poorly understood. Here, we generated chromosome‐level genomes for two sister species pairs of blind mole rats that differ in chromosome numbers. We identified five chromosome fusions during the divergence from a common ancestor (2n = 60). Three shared fusions gave rise to the Spalax galili (2n = 52)— S. golani (2n = 54) clade and accompanied its divergence from the S. carmeli (2n = 58)— S. judaei (2n = 60) clade. Both S. galili and S. carmeli further underwent an independent fusion. These fusions, facilitated by repetitive elements, were associated with changes in three‐dimensional genome architecture. Notably, we found reduced gene flow near fusion points. Chromosomal fusions correlated with signatures of selection and may have become fixed through centromeric repeat expansion. Together, these findings provide a genome‐wide framework for investigating how chromosomal fusions relate to genome organization and lineage divergence.

The Role of Atlantic Multidecadal Oscillation in Decadal Summer Temperature Variability Over the Tibetan Plateau in Observations and Pacemaker Simulations - Yanfeng He; Minhua Qin; Chuntao Yu; Huiting Feng; Hongwei Chen; Ming Li; Tao Wang; Min Wan; Shanlei Sun; Wenjian Hua (International Journal of Climatology, 2026)
Previous studies have suggested that internal oceanic modes such as the Interdecadal Pacific Oscillation (IPO) and Atlantic Multidecadal Oscillation (AMO) have significant effects on the decadal temperature variability over the Tibetan Plateau (TP). However, assessments of decadal variability are very sensitive to the length of study periods. Thus, the dominant factors regulating the decadal temperature variations over the TP and the associated mechanisms have not been clearly identified. This study utilised long‐term temperature observations, global reanalysis and climate model simulations to examine the decadal variations and the underlying mechanisms of surface air temperature (SAT) over the TP during boreal summer from 1901 to 2020. Results show that there exist decadal variations in summer TP SAT, with warm periods during 1929–1960 and 1999–2020 and cold periods during 1901–1928 and 1961–1998. It has also been found that the decadal changes in summer TP SAT are closely associated with the AMO. In contrast, TP SAT has a weak relationship with the IPO during 1901–2020. North Atlantic pacemaker simulations further show a zonal wave train pattern propagating from the North Atlantic to East Asia, which triggers anomalous anticyclonic circulations over the northern TP and Lake Baikal. The regional anticyclonic circulation anomalies over the TP not only weaken the subtropical westerly jet stream but also facilitate the water vapour transport into the TP and further cause local warming over the TP. Our findings elucidate the role of internal climate variability in shaping the decadal variability of summer TP SAT and also help reduce uncertainties in future projections of TP SAT changes.

Dietary silymarin improves gut–liver health by enhancing intestinal barrier integrity and modulating TLR4/NF-κB and NLRP3-mediated inflammatory responses in Aeromonas hydrophila–infected grass carp - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Hong-Yun Zhang; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Covalently assembled dual-functional triple-helix lentinan-Au for cervical cancer therapy - Xinjian Lu; Lei Feng; Li Zhang; Fengying Gu; Zuwei Liu; Haibo Xi; Hao Wan (Carbohydrate Polymers, 2026)

Study on the dynamic response and system reliability of curved beam bridge under multi-dimensional non-uniform random earthquake excitation - Xi-mei Li; Peng-hui Fan; Wan-run Li; Yong-feng Du (Soil Dynamics and Earthquake Engineering, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Palynological succession in Gzhelian No. 8 Thick Coal of the Taiyuan Formation, Ordos Basin, North China - Hui Zhang; Yun-He Shi; Peng-Shuai Jiao; Bo Pan; Feng Liu; Ming-Li Wan; Jing-Kun Zhang; Hui-Ping Peng (Palaeoworld, 2026)

Rice recruiting resilience-conferring Enterobacter via enhanced proline and malic acid exudation under thiamethoxam stress - Pei Wang; Fayun Feng; Mei Li; Faizan Ahmad; Qun Wan; Yong Li; Olubukola Oluranti Babalola; Kahsay Tadesse Mawcha; Jing Ge; Xiangyang Yu (Journal of Hazardous Materials, 2026)

Association of phthalate and substitute exposure with gestational liver function: A longitudinal cohort study - Xingxing Feng; Yuming Wang; Qi Chen; Hongbo Xu; Yanjian Wan; Yuanyuan Li; Hongxiu Liu; Shunqing Xu; Yan Zhou; Wei Xia (Environmental Research, 2026)

Integrating legume rotation and optimal nitrogen management enhances cotton yield and mitigates greenhouse gas emissions in a jujube-cotton intercropping system - Tiantian Li; Lu Feng; Jinbin Wang; Zhengjun Cui; Hang Qiao; Qiang Hu; Nan Cao; Ling Li; Wei Zhang; Mingwei Du; Yaru Zhao; Gulinigaer Taxi; et al. (European Journal of Agronomy, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Novel 2-aminothiazole derivatives incorporating 9-alkyl purine moiety: design, synthesis, crystal structure, and bioactivity evaluation - Song Bai; Suran Wan; Miao Li; Rong Wu; Shouying Tang; Fang Wang; Lijun Chen; Xiaokang Lv; Xian Wei; Shuang Feng; Miaohe Zhang (Molecular Diversity, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Lactate metabolism inhibition disrupts goat oocyte meiosis via H3K18la-mediated epigenetic dysregulation - Dongxu Li; Zhixuan Zhou; Minghui Zhu; Honglei Fan; Xinsong Xu; Honghui Lu; Feng Wang; Dagan Mao; Ziyu Wang; Yongjie Wan (Theriogenology, 2026)

Deciphering thermal behaviors of Qingchuan bitumen: Effects of atmosphere, heating rate, sample weight, kerogen, and clay minerals - Xianghui Zhang; Yuanyu Kou; Qin Liu; Huan Yang; Wei Hu; Xiangqi Leiyu; Hailong Wan; Wenling Yang; Xinyu Li; Junjie Wang; Ling Wang; Qian Feng (Fuel, 2026)

Flavor characteristics of traditional and mechanically processed base baijiu of sauce-flavor baijiu revealed by GC-IMS and GC-MS - Ruiqi Liu; Jialiang Niu; Bo Wan; Feng Hu; Cheng Wu; Junlin Yang; Anran Zhu; Baoguo Sun; Xiuting Li (Food Chemistry, 2026)

Effect of ciprofloxacin on performance, antibiotic resistance genes, and microbial communities in mesophilic anaerobic codigestion enriched with Methanosarcina and a recovery strategy after collapse - Bao-Shan Xing; Yong-Ning Feng; Su Li; Liguo Wan; Yi-Fan Wu; Xiaochang C. Wang; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2026)

Synergistic engineering of selenium vacancies and heterojunctions in MoSe2/Sb2Se3/C for fast and ultra-stable sodium-ion storage - Zhixin Wan; Fengzhi Li; Feng Jiang; Chao Wang; Junzhe Li; Hanyue Zhao; Yangzhou Ma; Jie Xu; Chao Yang (Chemical Engineering Journal, 2026)

Transcriptional condensates enrich phosphorylated PRMT2 to stimulate H3R8me2a deposition and hypoxic response in glioblastoma - Feng Dong; Xuan Cheng; Jiaxiang Wan; Qian Li; Weijian Du; Wei Li; Xiaoyu Sun; Xudong Wu (Science China Life Sciences, 2026)

Solidified dredged sediment as ecological restoration substrate: mechanical strength, water stability, and vegetation performance - Ying Zhu; Siyao Chen; Feng Zhong; Xingxing He; Yong Wan; Menghao Li; Gaopeng Shen (Journal of Soils and Sediments, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Unraveling the impact of microplastics on autoimmune diseases: hidden dangers and environmental triggers - Yu-Tong Tan; Wei-Wei Wang; Shu-Zhen Xu; Yu-Wan Chang; Lei Li; Peng Wang; Hai-Feng Pan (Environmental Geochemistry and Health, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Storm water management model simulations of the non-point source pollution load in the northern Anhui plain - Yun Wan; Mingjun Li; Nan Zhang; Mengwan Lin; Yuxuan Li; Peiqing Huang; Yuqi Feng; Bai Sun; Wei Wei; Shuguang Zhu (Ecohydrology & Hydrobiology, 2025)

Biomass-derived fluorescent carbon dots from Ginkgo biloba leaves: A dual-functional nanomaterial for bioimaging and diabetic wound healing - Mingxin Li; Mengzhen Xu; Wen Su; Feng Zhao; Mohan Hao; Hanxiang Wang; Haoran Yue; Qingjun Zhu; Wei Li; Ruiying Wan; Haixing Guan (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

Research on the Mechanism of Complex Water-flooded Layers and Well Logging Evaluation Methods in the M Oilfield - Wen-Yuan He; Ya-Dong Wu; Li-Xiang Feng; Chang-Xi Li; Jin-Bin Wan; Guo-Hui Ni (Applied Geophysics, 2025)

Constructing an effective exposure index through mobile signal data in guangzhou: a refined resilience assessment of COVID-19-Driven shifts in urban green space usage - Jintang Chen; Luyao Yang; Shan Li; Bin Chen; Wanjun Lu; Fengdeng Wan; Qiumeng Li; Yongheng Feng (Urban Forestry & Urban Greening, 2025)

Promoting acetate production on the in situ reconstructed Cu nanoislands via pressure-regulated CO adsorption and electroreduction - Rongxing Qiu; Jiaran Li; Jiafeng Du; Siwang Zhang; Lingzhi Ding; Jinlong Wan; Cheng Li; Jinyu Ye; Jin-Chao Dong; Yuanjie Pang; Jian-Feng Li; Shuliang Yang; et al. (Science Bulletin, 2025)

Electro Fenton degradation of glyphosate by incrassated defect-free conductive Cu metal organic framework - Wenlong Xu; Ke Chen; Yongdan Yang; Qinyi Wan; Yanan Huang; Zhenhao Zhou; Yuan Li; Xin Zhou; Yingying Ma; Emad M. Hafez; Anis Ali Shah; Youzhi Feng; et al. (Process Safety and Environmental Protection, 2025)

Fundamental research on recycling spent lithium-ion batteries for environmental pollutant control - Lizhen Feng; Chuanqi Pan; Baozhong Zhang; Lijuan Liu; Jingwei Wan; Shengfeng Cui; Wei Li (Journal of Environmental Management, 2025)

Development of fully bio-based eco-resin with integrated flame Retardancy, high flexibility, and degradability from vegetable oil-polysaccharide hybrid systems - Fulu Wang; Changxin Wan; Haodan Li; Yuhang Li; Feng Hu; Youwei Liao; Yan Yang (Chemical Engineering Journal, 2025)

A non-invasive method for sexing all castes of Prorhinotermes flavus (Blattodea: Psammotermitidae) using external morphology - Wan-Jen Li; Yi-Ning Chiu; Hauchuan Liao; Hou-Feng Li (Arthropod Structure & Development, 2025)

Synergistic effects of slow-release fertilizer and biochar on crop yield and soil carbon-nitrogen dynamics under reduced nitrogen input - Lianhao Zhao; Wen Yin; Qiang Chai; Pan Li; Zhipeng Guo; Zhilong Fan; Falong Hu; Cai Zhao; Aizhong Yu; Pingxing Wan; Wei He; Hong Fan; et al. (Agriculture, Ecosystems & Environment, 2025)

Multi-branch spatial-spectral fusion with hybrid convolutional and multi-head cross-patch attention for hyperspectral image classification - Xiaoqing Wan; Ziqi Sun; Yupeng He; Feng Chen; Zhize Li; Weizhe Gao (Advances in Space Research, 2025)

Eukaryotic Plankton Exhibit High Community Connectivity in the Indo‐Pacific Convergence Zone Across Tropical and Subtropical Oceans - Longzhao Li; Feng Zhao; Ariani Hatmanti; Weiyue Liu; Yuanyuan Wan; Tingting Yin; Kuidong Xu (Journal of Biogeography, 2025)
Aim Eukaryotic plankton distribution is considered not limited by dispersal in oceans. However, the Tara Oceans expedition indicated eukaryotic plankton communities are homogenised only at basin scale. Community connectivity of plankton remains largely unexplored. Here, surface seawater samples were collected from the Indo‐Pacific Convergence Zone (IPCZ), combined with the reanalysis of the Copernicus data and data of 35 stations from the Tara Oceans, to explore community connectivity across global oceans. Location The IPCZ and tropical and subtropical oceans. Time From 2021 to 2022. Taxa Eukaryotic plankton. Methods We performed a meta‐analysis of the Tara Oceans and Copernicus database and samples collected from the IPCZ to investigate eukaryotic plankton diversity and connectivity through metabarcoding. Results About 11% of eukaryotic plankton were ubiquitous based on the Tara Oceans data, and 20%–30% were shared by adjacent basins. The highest proportion was shared by the Indian Ocean (IO) and the Pacific Ocean (PAC). In the IPCZ, communities of the PAC and IO were more similar with a higher diversity compared with those from marginal seas. Salinity explained the differences between the ocean and marginal sea communities. The contribution of eukaryotic plankton community in the ocean to that in marginal seas was more than that of marginal seas to the ocean, which was consistent with the centre of accumulation hypothesis. In spring, eukaryotic plankton were transported from the PAC to IO through the South China Sea (SCS) and Sunda Strait. In summer, they were transported from the IO to SCS through the Malacca Strait under monsoon influence. Dispersal ability of different taxonomic groups in certain regions was similar, but community connectivity varied. Conclusions Eukaryotic plankton community exhibits high connectivity in the IPCZ across tropical and subtropical oceans. Ocean currents are important carriers of microbial dispersal, while monsoon‐driven hydrographic variations, particularly salinity fluctuations, shape community connectivity.

Small-mammalian fossils from the Paleolithic Dayin Cave site in Yunnan, Southwest China - Yinan Zhang; Feng Gao; Yang Wan; Fan Yang; Bin Gao; Yueming Zeng; Bo Liu; Zetao Zhang; Wenwei Huang; Weiming Wang; Qiang Li; Xijun Ni (Quaternary International, 2025)

Prospective associations of in utero exposure to multiple insecticides with cord blood mitochondria DNA copy number and longitudinal offspring telomere length shortening - Feng Qiu; Yanjian Wan; Aizhen Wang; Gaga Mahai; Yujie He; Wensi Zhou; Ying Zhu; Wei Xia; Shunqing Xu; Yuanyuan Li (Journal of Hazardous Materials, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

Automated high-purity fast-flow synthesis of cyclic peptide-PNA conjugates for drug discovery and nanotechnology - Wanglin Zhan; Feng Wan; Xingxing Yang; Hongliang Duan; Chengxi Li (Chemical Engineering Journal, 2025)

Identification of joint probability distribution for thermal parameters of warm frozen clay with incomplete probability information - Hao Li; Tao Wang; Yonglin Feng; Jiazeng Cao; Yutong Song; Guoqing Zhou; Weifeng Wan (Cold Regions Science and Technology, 2025)

Hesperetin ameliorates mitochondrial dysfunction in acute kidney injury by mediating autophagy and inhibiting the cGAS-STING pathway - Pei Cao; Wan Zhu; Deng Li; JiGang Zhang; Xing Feng (Journal of Molecular Histology, 2025)

Development and application of InDels and SNPs markers based on whole-genome resequencing in Chinese cabbage - Kai-Wen Liu; Wan-Jie Men; Jin-Xia Feng; Iqbal Hussain; Hui Sheng; Li-Wei Zhang; Zhong-Ren Dai; Hai-Jiang Hu; Jian-Hao Yang; Na Lei; Xiao-Lin Yu (Horticulture, Environment, and Biotechnology, 2025)

Cold atmospheric plasma-derived ROS detoxifies deoxynivalenol-induced nephrotoxicity - Ruonan Ma; Junxia Feng; Hangbo Xu; Xiaoying Zhou; Chunli Liu; Guoyu Zhou; Dongjie Cui; Yupan Zhu; Junhu Wan; Dezheng Yang; Gautam Sethi; Xudong Yang; et al. (Journal of Hazardous Materials, 2025)

Growth-promoting bacterium Enterobacter sp. CS8-gfp triggers jasmonate signaling pathway for atrazine and thiamethoxam degradation in rice (Oryza sativa L.) - Li Ya Ma; Qun Wan; Jing Ge; Yong Li; Fayun Feng; Mei Li; Jinjin Cheng; Jian Chen; Ya Wang; Yaoyao Cao; Chenye Yang; Xiangyang Yu (Journal of Cleaner Production, 2025)

Catalytic fast pyrolysis of waste battery separators with limited removal of the Al2O3 layer for selective aromatic hydrocarbons production over HZSM-5 catalyst - Li Zhao; Wan-zhao Huang; Shi-guan Yang; Qi Niu; Shi-yu Feng; Pu-cheng Wang; Ying Mo; Yu-han Fan; Kai Li; Qiang Lu (Journal of Environmental Management, 2025)

Comparative assessment of thyroid disrupting effects of ethiprole and its metabolites: In silico, in vitro, and in vivo study - Zheyuan Song; Zheng Ma; Xueshan Feng; Rui Huang; Qiong An; Yunrui Pan; Jing Chang; Bin Wan; Huili Wang; Jianzhong Li (Journal of Environmental Sciences, 2025)

Experimental investigation and numerical analysis on fire response of parallel-wire cable exposed to open-air fire - Hao Wan; Gang Zhang; Feng Xu; Yuhang Ding; Mingxuan Li (Engineering Structures, 2025)

Nitrogen and oxygen dual-doped carbon catalysts derived from saccharides and dicyandiamide for electrocatalytic O2 reduction to H2O2: Effect of saccharide type and elucidation of active sites - Yanan Liu; Kun Wan; Danning Feng; Zhaoli Yang; Yan Pei; Minghua Qiao; Hexing Li; Baoning Zong (Chemical Engineering Journal, 2025)

Production of docosahexaenoic acid from corncob residue wastes through integrated whole-cell lignocellulosic saccharification and lipid fermentation by Aurantiochytrium - Xiaojin Song; Weijian Wan; Yuedong Zhang; Guang Yu; Bin Li; Qiu Cui; Ya-Jun Liu; Yingang Feng (Bioresource Technology, 2025)

Responses of plant community drought resistance and resilience to warming and nitrogen addition vary with recurrent droughts in a semi-arid grassland - Haidao Wang; Jian Song; Yongge Fan; Jianyang Xia; Lin Jiang; Qingshan Zhang; Heng Li; Jingyi Ru; Jiayin Feng; Lingjie Kong; Jiajun Zhang; Xueli Qiu; et al. (Agriculture, Ecosystems & Environment, 2025)

Corrigendum to "Peganutonin A, a novel melatonin analogue from the seeds of Peganum harmala" [Phytochem. Lett. 56 (2023) 78–80] - Jian-Bo Liu; Wan-Ying Li; Xue Zhao; Feng-Ying Yang; Lei Fang (Phytochemistry Letters, 2025)

Inversion of airborne tipper and ground-based data for two-dimensional radio-magnetotelluric using the Gauss-Newton method - Ke Yi; Zhiyong Zhang; Feng Zhou; Man Li; Jianhua Wan; Lei Huang; Hongze Deng (Journal of Applied Geophysics, 2025)

Erosion processes of lahar travelling on volcanic sediments: Insights from the physical and numerical modeling - Shengwu Qin; Jiangfeng Lv; Shuangshuang Qiao; Junjun Chen; Feng Wan; Jingyu Yao; Guangjie Li; Lingshuai Zhang (CATENA, 2025)

Mulberry Diels-Alder-type adducts and other phenolic compounds with ATP-citrate lyase inhibitory effects from Morus alba and their chemotaxonomic significance - Qi Zhou; Ying-Peng Tong; Jiang Wan; Li-Hong Yan; Chun-Xiao Jiang; Jin-Feng Hu (Biochemical Systematics and Ecology, 2025)

New insights into rhizosphere bacterial community shaped by lettuce genotypes for divergent degradation efficiencies of phthalates - Guang-Xuan Tang; Yu-Hong Huang; Li-Wan Feng; Yu-Chang Hu; Jia-Lu Wei; Huixiong Lü; Li-Hui Liu; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; et al. (Journal of Hazardous Materials, 2025)

Correction for calcium interference in the 40Ar/39Ar dating method - Wan-Feng Zhang; Jun-Jie Wang; De-Wen Zheng; Ming Xiao; Jia Zhang; Jun-Jie Li; Yu-Lian Zhang; Ying-De Jiang; Fei Su; Li Li; Yi-Gang Xu (Icarus, 2025)

Multifunctional chitosan-based indicator films containing composite pigments stabilized by extracellular and cell wall polysaccharides from Auricularia cornea var. Li. waste for visualization of salmon freshness - Shuanglong Yang; Keshu Lu; Xueying Shi; Shuhan Xu; Binyan Li; Xin Feng; Tiejing Li; Wentao Su; Yujun Wan; Xiangyu Cao; Yuxiao Wang (Food Chemistry, 2025)

Different Expression Patterns and Interactions with Time Recorder DAL1 Revealed the Gene Expansion and Functional Differentiation of Flowering Integrator SOC1 During Larch Aging - Zha-Long Ye; Xiang-Yi Li; Dong-Xia Cheng; Wan-Feng Li (Journal of Plant Growth Regulation, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Soybean 7S protein/calcium phosphate complexes for enhanced probiotic delivery and gut microbial regulation - Kaining Han; Guangxin Feng; Tanghao Li; Zhili Wan; Jian Guo; Xiaoquan Yang (Food Bioscience, 2025)

Butterfly-inspired structures on strong and tough metagel for enhanced passive radiative and evaporative cooling - Di Han; Jipeng Fei; Yongping Long; Yuanhang Yang; Anna Lushnikova; Hiba Mhiri; Christophe Ménézo; Man Pun Wan; Hong Li; Xuan Zhang; Bing Feng Ng (Chemical Engineering Journal, 2025)

Geochemical evidence of paleo-pacific slab melting in the big mantle wedge beneath Northeast China during the Early Cretaceous - Chao-Yang Liu; Hong-Yan Li; Yi-Gang Xu; Qiang Ma; Chun Yang; Wan-Feng Zhang (Chemical Geology, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

New perspectives on the immune regulatory role of dietary silymarin in the intestines of juvenile grass carp (Ctenopharyngodon idella) - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Enhanced activation of peroxymonosulfate by nickel sulfide with sulfur vacancies for ultrafast organic pollutants degradation: Roles of active sites and mechanism - Cai-Wu Luo; Liang Jiang; Xian-Feng Li; Qiang-Mao Wan; Tian-Jiao Jiang; Sen-Ping Mao; Jing-Qian Guo; Run-Ze Zhao; Chao Xie (Environmental Pollution, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Chemical constituents of Xylanche himalaica and their chemotaxonomic significance - Wei Nie; Li-Ping Feng; Jin-Fu Wan; Xiao-Hui Li; Ying-Jie Zhang; De-Huan Fu; Qian Li (Biochemical Systematics and Ecology, 2025)

PpSPL1 and PpSPL15 inhibit peach branching by increasing strigolactone synthesis - Wan Pei; Jie Zhang; Ruixian Shen; Hefang Xie; Yajia Zhang; Junjie Zhang; Xiaodong Lian; Haipeng Zhang; Nan Hou; Lei Wang; Xianbo Zheng; Jun Cheng; et al. (Planta, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Discovery of bi-4-methoxycarbonyl-2-quinolone and evaluation of its anti-inflammatory and anti-cancer activity in vitro - Wenmin Wang; Xiao He; Yang Wan; Daofeng Chen; Zhifeng Li; Yulin Feng; Quan Wen (Natural Product Research, 2025)

Earthworms buffer the impacts of nitrogen enrichment on energy dynamics of soil micro-food webs - Bingbing Wan; Andrew D. Barnes; Mingyu Li; Yuanyuan Song; Qian Yang; Xiaoyun Chen; Feng Hu; Manqiang Liu (Soil Biology and Biochemistry, 2025)

Genomic, transcriptomic, and metabolomic analyses reveal convergent evolution of oxime biosynthesis in Darwin’s orchid - Kai Jiang; Birger Lindberg Møller; Shaofan Luo; Yu Yang; David R. Nelson; Elizabeth Heather Jakobsen Neilson; Joachim Møller Christensen; Kai Hua; Chao Hu; Xinhua Zeng; Mohammed Saddik Motawie; Tao Wan; et al. (Molecular Plant, 2025)

Construction and characterization of probiotic intestinal-targeted delivery system based on complex coacervation and double-emulsion structure - Nuocheng Xu; Yutong Feng; Huiping Wan; Zilong Li; Keyu Sun; Shuhong Ye (Food Hydrocolloids, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Innovative use of wastewater-extracted Arabinoxylans: Elevating steamed bread texture and structure - Jiahao Wan; Yifan Wei; Yunhui Zhang; Honglin Lan; Xingguo Li; Yanbin Wang; Denglin Luo; Junwei Feng; Zhouya Bai; Jinying Guo (Food Chemistry, 2025)

Structure-rheological relationship of capillary protein oleogels: The role of particle wettability - Gao-Shang Wang; Long-Yuan Zhang; Guang-Xin Feng; Chuan-Wu Han; Li-Juan Wang; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2025)

Comprehensive suitability assessment of fish habitat by integrating mechanism model and bayesian network model - Yuliang Yuan; Ran Li; Jingjie Feng; Hang Wan; Honghui Lin; Xiaolong Cheng (Ecological Engineering, 2025)

Mantle induced hydration and oxidation of intracontinental granite sources in the North China Craton - Chuan-Mao Yang; Yi-Gang Xu; Xiao-Ping Xia; Jin-Hui Yang; Xiao-Long Huang; Christopher J. Spencer; Jin-Feng Sun; Ze-Xian Cui; Meng-Jing Li; Wan-Feng Zhang; Qing Yang (Earth and Planetary Science Letters, 2025)

Tree biology: From genomics to genetic improvement - Jinbo Shen; Wan-Feng Li; Chang Liu; Shuai Zheng (Plant Science, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

Recent progress and perspectives of single-atom catalysts with framework architecture for zinc-air battery cathodes - Zekun Zhang; Jia Dong; Chunting Huang; Kexin Wan; Zemin Feng; Bin Li; Ningning Zhao; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2025)

Maize promoted the growth and volatile oil accumulation of Atractylodes lancea through rhizosphere VOCs - Zheng Peng; Meiyu Cao; Binbin Yan; Sheng Wang; Chuangzhi Kang; Hongyang Wang; Xiufu Wan; Qingxiu Hao; Zengxu Xiang; Zihua Zhang; Wenjun Xue; Li Feng; et al. (Plant and Soil, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Evaluating the impact of dermal absorption on internal doses of dechlorane plus in Chinese e-waste recycling employees - Yao-Yuan Wan; Xiao-meng Cheng; Xing-Hong Li; Feng-Shuang Wang; Yuan-Yuan Li; Jing Li; Zhan-Fen Qin (Chemosphere, 2024)

Temperature sensitivity of soil respiration to elevated temperature and nitrogen availability - Yufei Li; Kaiping Zhang; Yuling Li; Pingxing Wan; Zhongke Zhou; Wucheng Zhao; Ningning Zhang; Ning Chai; Zhixin Li; Yalan Huang; Feng Zhang (Soil and Tillage Research, 2024)

Major specialized natural products from the endangered plant Heptacodium miconioides, potential medicinal uses and insights into its longstanding unresolved systematic classification - Ze-Yu Zhao; Jiang Wan; Hao-Wei Chen; Zhong-Shuai Sun; Yu-Tian Tao; Yingpeng Tong; Yi Zang; Yeun-Mun Choo; Pan Wang; Yue-Ling Li; Chun-Xiao Jiang; Junming Li; et al. (Phytochemistry, 2024)

Enhanced creaminess of plant-based milk via enrichment of papain hydrolyzed oleosomes - Biao Li; Chuanwu Han; Guangxin Feng; Jian Guo; Zhili Wan; Xiaoquan Yang (Food Research International, 2024)

Insight into the mechanism of alkyl polyglucose biosurfactants enhancing antibiotics resistance genes removal during biotransformation of waste activated sludge into medium-chain fatty acids - Chun-shuang Zhou; Guang-li Cao; Bing-feng Liu; Sheng-qiang Fan; Wan-li Ma; Nan-qi Ren (Chemical Engineering Journal, 2024)

Advanced growing-season precipitation peak promotes soil nitrogen mineralization in a semi-arid grassland - Jiayin Feng; Xiaojing Yue; Benqing Li; Jingyi Ru; Zhenxing Zhou; Lingjie Kong; Jiajun Zhang; Jiaxin Zhou; Guilin Zhou; Wenjing Ma; Yaru Lyu; Jian Song; et al. (CATENA, 2024)

Kinetic study on the effect of ice nucleation and generation on methane hydrate dissociation below the quadruple point - Ting-Ting Zhang; Bo Li; Wen-Na Wei; Jing-Chun Feng; Qing-Cui Wan (Gas Science and Engineering, 2024)

Wheat genetic progress in biomass allocation and yield components: A global perspective - Yue Xi; Yan-Lei Du; Dong Wang; Jie-Ying Ren; Wen-Yuan Luo; Qiao Peng; Wan-Ying Fang; Feng-Min Li (Field Crops Research, 2024)

Enhancing medium-chain fatty acids production via alkyl polyglucose modulation of electron acceptor generation, microbial community and metabolic traits in anaerobic fermentation of waste activated sludge - Chun-shuang Zhou; Guang-li Cao; Bing-feng Liu; Guo-jun Xie; Wan-li Ma; Sheng-qiang Fan; Nan-qi Ren (Chemical Engineering Journal, 2024)

A novel dual-ligand copper-based nanoflower for the colorimetric and fluorescence detection of 2,4-dichlorophenol, epinephrine and hydrogen peroxide - Jia-Xin Li; Tong-Qing Chai; Guo-Ying Chen; Mao-Ling Luo; Jian-Bo Wan; Feng-Qing Yang (Analytica Chimica Acta, 2024)

Changes in plant litter and root carbon inputs alter soil respiration in three different forests of a climate transitional region - Jiayin Feng; Chunyu Wang; Jingjing Gao; Huixia Ma; Zheng Li; Yuanfeng Hao; Xueli Qiu; Jingyi Ru; Jian Song; Shiqiang Wan (Agricultural and Forest Meteorology, 2024)

Provenance and transport mechanism of marine sediments in the Zhongjiannan Basin - Xuewan Wu; Chaoqi Shi; Feng Guo; Zihan Li; Junsheng Luo; Peipeng Li; Ziwen Wang; Guifeng Wang; Zhifeng Wan (Frontiers in Marine Science, 2024)
The research on the source of marine sediments has a vital impact on identifying material sources, transport mechanism, and the evolution of sedimentary environments. Previous studies have shown many outstanding achievements on the source analysis of the South China Sea, but there are still some controversies over the complex source and transport mechanisms of the Zhongjiannan Basin. In this study, we took a gravity core (583cm) from the Zhongjiannan Basin and analyzed the particle size, rare earth elements, and Sr-Nd isotopes of the core sediments to further reveal the source and transport mechanism. The surface sediments in the Zhongjiannan Basin were relatively stable, with an average particle size ranging from 5.66 to 17.74 μm. The normalized standard curve of chondrite exhibited the depletion of Eu, with LREE dominated in REE. As the depth increased, 87 Sr/ 86 Sr ratios showed a gradually increasing trend, while δNd change was relatively complex. On the whole, 87 Sr/ 86 Sr ratios (from 0.721537 to 0.725322) and δNd (from -11.561617 to -12.289374) were in a relatively narrow range. Based on the particle size characteristics, we found the geochemical characteristics of sediment largely resulted from different sediment sources. By comparing rare earth elements and Sr-Nd isotopes, we concluded the sediment of the Zhongjiannan Basin was from mainly terrigenous contribution. In addition, taking into account factors such as terrain, migration distance, and river drainage system, we conclude the sediment were mainly from the Mekong River, the Red River, Taiwan Island, and Hainan Island. The surface current along the northeast direction was the main transportation route for the sediments of the Mekong River. The Guangdong coastal current and the southwest surface current transported sediment from the Red River and Hainan Island to the Zhongjiannan Basin. The surface current and deep-water current in the southwest direction carried sediment from Taiwan Island to the study area, while the Kuroshio also had some impacts on the sediment transportation of Taiwan Island. This study has reinforced the research on provenance in the South China Sea Basin and has an important significance on evolution of sedimentary environments, evolution of ancient oceans.

Machine learning for high-precision simulation of dissolved organic matter in sewer: Overcoming data restrictions with generative adversarial networks - Feng Hou; Shuai Liu; Wan-Xin Yin; Li-Li Gan; Hong-Tao Pang; Jia-Qiang Lv; Ying Liu; Hong-Cheng Wang (Science of The Total Environment, 2024)

P-phenylenediamine antioxidants and their quinone derivatives: A review of their environmental occurrence, accessibility, potential toxicity, and human exposure - Yuting Liang; Feng Zhu; Jie Li; Xin Wan; Yiling Ge; Geyu Liang; Yonglin Zhou (Science of The Total Environment, 2024)

Topological surface states in quasi-two-dimensional magnetic kagome metal EuTi3Bi4 - Zhicheng Jiang; Tongrui Li; Jian Yuan; Zhengtai Liu; Zhipeng Cao; Soohyun Cho; Mingfang Shu; Yichen Yang; Zhikai Li; Jiayu Liu; Jianyang Ding; Zhonghao Liu; et al. (Science Bulletin, 2024)

Cytotoxic steroidal glycosides from Paris rugosa rhizomes - Jian-Ke Jia; Jun Yang; Xing-Zhi Yang; Ji-Feng Luo; Xiao-Yan Duan; Ying-Li Yang; Jin-Fu Wan; Yue-Hu Wang (Phytochemistry Letters, 2024)

Alkali pretreatment-assisted catalytic pyrolysis of waste cellulose acetate for selective preparation of levoglucosenone - Shi-Yu Feng; Sheng Li; Wan-Zhao Huang; Qi Niu; Deng-Yu Chen; Zhi-Mo Fang; Li-Juan Gao; Kai Li; Qiang Lu (Journal of Environmental Chemical Engineering, 2024)

Overlapping hotspot tracks and melts from diffuse plume materials in the upper mantle generated intraplate seamount groups in the West Pacific - Xun Wei; Guo-Liang Zhang; Ji Zhang; Xue-Fa Shi; Paterno R. Castillo; Yan Zhang; Wan-Feng Zhang; Yi-Gang Xu; Hong-Yan Li; Hui Zhang (Earth and Planetary Science Letters, 2024)

Plasmalogens and Octanoylcarnitine Serve as Early Warnings for Central Retinal Artery Occlusion - Chuansen Wang; Ying Li; Jiaqing Feng; Hang Liu; Yuedan Wang; Yuwei Wan; Mengxue Zheng; Xuejie Li; Ting Chen; Xuan Xiao (Molecular Neurobiology, 2024)
Central retinal artery occlusion (CRAO) is a kind of ophthalmic emergency which may cause loss of functional visual acuity. However, the limited treatment options emphasize the significance of early disease prevention. Metabolomics has the potential to be a powerful tool for early identification of individuals at risk of CRAO. The aim of the study was to identify potential biomarkers for CRAO through a comprehensive analysis. We employed metabolomics analysis to compare venous blood samples from CRAO patients with cataract patients for the venous difference, as well as arterial and venous blood from CRAO patients for the arteriovenous difference. The analysis of metabolites showed that PC(P-18:0/22:6(4Z,7Z,10Z,13Z,16Z,19Z)), PC(P-18:0/20:4(5Z,8Z,11Z,14Z)) and octanoylcarnitine were strongly correlated with CRAO. We also used univariate logistic regression, random forest (RF), and support vector machine (SVM) to screen clinical parameters of patients and found that HDL-C and ApoA1 showed significant predictive efficacy in CRAO patients. We compared the predictive performance of the clinical parameter model with combined model. The prediction efficiency of the combined model was significantly better with area under the receiver operating characteristic curve (AUROC) of 0.815. Decision curve analysis (DCA) also exhibited a notably higher net benefit rate. These results underscored the potency of these three substances as robust predictors of CRAO occurrence.

Decoded EEG neurofeedback-guided cognitive reappraisal training for emotion regulation - Linling Li; Xueying Gui; Gan Huang; Li Zhang; Feng Wan; Xue Han; Jianhong Wang; Dong Ni; Zhen Liang; Zhiguo Zhang (Cognitive Neurodynamics, 2024)

Theoretical analysis of naproxen reaction with sulfate and hydroxyl radicals in the aqueous phase: Investigating reactive sites and reaction kinetics - Ji-Feng Yang; Wan-Li You; Deng You; Li-Ying Zheng; Jun-Ling Jin; Sheng-Lian Luo (Chemosphere, 2024)

Unveiling the fate of metal leaching in bimetal-catalyzed Fenton-like systems: pivotal role of aqueous matrices and machine learning prediction - Wenrui Jia; Ying Li; Chuchu Chen; Yaohua Wu; Yongqi Liang; Juanshan Du; Xiaochi Feng; Huazhe Wang; Qinglian Wu; Wan-Qian Guo (Journal of Hazardous Materials, 2024)

Rapid evaluation of the quality of Smilax glabra Roxb. using QADS based on FT-NIR combined with multiple intelligent algorithms - Geng-zhi Zhan; Xin-yue Guo; Zi-chao Qiu; Lu-yao Cai; Qian Hu; Ye Gao; Shu-wan Tang; Cun-yu Li; Yun-feng Zheng; Guo-ping Peng (Food Chemistry, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Additive effects of N addition and changing precipitation on soil respiration in a climate transitional forest - Jiayin Feng; Jingjing Gao; Huixia Ma; Chunyu Wang; Yuanfeng Hao; Zheng Li; Jingru Zou; Xueli Qiu; Jingyi Ru; Jian Song; Shiqiang Wan (CATENA, 2024)

Actn2 defects accelerates H9c2 hypertrophy via ERK phosphorylation under chronic stress - Kang Wang; Ye Wang; Hua Wan; Jie Wang; Li Hu; Shuainan Huang; Mingchen Sheng; Jiayi Wu; Xing Han; Youjia Yu; Peng Chen; Feng Chen (Genes & Genomics, 2024)

Temperature dependence of the rain-gas and snow-gas partition coefficients for nearly a thousand chemicals - Pu-Fei Yang; Wan-Li Ma; Hang Xiao; Kaj M. Hansen; Liang Wang; Jing-Jing Sun; Li-Yan Liu; Zi-Feng Zhang; Hong-Liang Jia; Yi-Fan Li (Chemosphere, 2024)

New perspectives on the role of vitamin D in the mucosal barrier system of fish gills infected with Flavobacterium columnare - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Lu Zhang; Hai-Feng Mi; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2024)

Periodic inundation accelerates the release process of organic carbon from plant litter - Zhonghang Wu; Mao Ye; Ran Li; Jingjie Feng; Hang Wan; Xiaolong Cheng (Journal of Environmental Management, 2024)

Isophorone-based crystallization-induced-emission sensors detect proteome aggregation in live cells and tissues with breast cancer - Xiaomeng Jia; Di Shen; Jintai Deng; Kainan Wang; Xueqing Wang; Yijin Guo; Lu Sun; Hao Jin; Qiuxuan Xia; Huan Feng; Biao Jing; Jialu Sun; et al. (Analytica Chimica Acta, 2024)

Experimental investigation on compressive dwell fatigue behavior of titanium alloy pressure hull for deep-sea manned submersibles - Lei Wang; Cong Ye; Chengqi Sun; Shichao Feng; Xiaozhong Xie; Yuan Gao; Kun Zhao; Yanqing Li; Zhengquan Wan (Ocean Engineering, 2024)

Deciphering the reduction of antibiotic resistance genes (ARGs) during medium-chain fatty acids production from waste activated sludge: Driven by inhibition of ARGs transmission and shift of microbial community - Chun-shuang Zhou; Guang-li Cao; Bing-feng Liu; Wei Liu; Wan-li Ma; Nan-qi Ren (Journal of Hazardous Materials, 2024)

Pollution characteristics, source apportionment and absorption spectra of size-resolved PAHs in atmospheric particles in a cold megacity of China - De-Qi Wang; Shi-Ming Jia; Li-Yan Liu; Zi-Feng Zhang; Fu-Jie Zhu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

Dynamic changes and the effects of key procedures on the characteristic aroma compounds of Lu’an Guapian green tea during the manufacturing process - Jieyao Yu; Jingzhe Li; Zhi Lin; Yin Zhu; Zhihui Feng; Dejiang Ni; Shengchun Zeng; Xuehong Zeng; Yijun Wang; Jingming Ning; Liang Zhang; Xiaochun Wan; et al. (Food Research International, 2024)

Anti-inflammatory activity of organic acids from the seeds of Phaseolus lunatus L. - Kun Li; Jin-hui Bian; Heng Wu; Ya-lan Wang; Yun-jia Feng; Jia Nie; Na Chen; Han Yu; Wan Li; Yu-zhu Tan; Guang-hua Lu (Phytochemistry Letters, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Study on the habitat evolution after dam removal in a habitat-alternative tributary of large hydropower station - Zhenhua Wang; Jingjie Feng; Tao He; Jiuxian Yang; Hang Wan; Yuliang Yuan; Ran Li (Journal of Environmental Management, 2024)

Linear and nonlinear rheological characterization of capillary protein oleogels as potential fat replacers: Comparison with high internal-phase emulsions - Gao-Shang Wang; Qing Li; Guang-Xin Feng; Chuan-Wu Han; Jian Guo; Jin-Mei Wang; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Massively parallel implementation of iterative eigensolvers in large-scale plane-wave density functional theory - Junwei Feng; Lingyun Wan; Jielan Li; Shizhe Jiao; Xinhui Cui; Wei Hu; Jinlong Yang (Computer Physics Communications, 2024)

Protein-assisted synthesis of chitosan-coated minicells enhance dendritic cell recruitment for therapeutic immunomodulation within pulmonary tumors - Jing Feng; Yiting Liu; Xiaoran Zheng; Min Gao; Li Wang; Lígia R. Rodrigues; Yuting Wen; Hangcheng Pan; Gege Li; Longjiang Zhang; Bing Wan; Yunlei Zhang (Carbohydrate Polymers, 2024)

Multimodal and hemispheric graph-theoretical brain network predictors of learning efficacy for frontal alpha asymmetry neurofeedback - Linling Li; Yutong Li; Zhaoxun Li; Gan Huang; Zhen Liang; Li Zhang; Feng Wan; Manjun Shen; Xue Han; Zhiguo Zhang (Cognitive Neurodynamics, 2024)

New Record Ocean Temperatures and Related Climate Indicators in 2023 - Lijing Cheng; John Abraham; Kevin E. Trenberth; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Fujiang Yu; Ricardo Locarnini; John Fasullo; Fei Zheng; Yuanlong Li; et al. (Advances in Atmospheric Sciences, 2024)
The global physical and biogeochemical environment has been substantially altered in response to increased atmospheric greenhouse gases from human activities. In 2023, the sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached record highs. The 0–2000 m OHC in 2023 exceeded that of 2022 by 15 ± 10 ZJ (1 Zetta Joules = 10 21 Joules) (updated IAP/CAS data); 9 ± 5 ZJ (NCEI/NOAA data). The Tropical Atlantic Ocean, the Mediterranean Sea, and southern oceans recorded their highest OHC observed since the 1950s. Associated with the onset of a strong El Niño, the global SST reached its record high in 2023 with an annual mean of ∼0.23°C higher than 2022 and an astounding > 0.3°C above 2022 values for the second half of 2023. The density stratification and spatial temperature inhomogeneity indexes reached their highest values in 2023.

Occurrence and fate of pharmaceuticals and personal care products in a wastewater treatment plant with Bacillus bio-reactor treatment - Xi-Ze Min; Zi-Feng Zhang; Xi-Mei Lu; Jia-Cheng Chen; Wan-Li Ma; Li-Yan Liu; Wen-Long Li; Yi-Fan Li; Roland Kallenborn (Science of The Total Environment, 2024)

Lateral migration of methane at a cold seep: Evidence from U–Th dating of methane-derived authigenic carbonate in the Middle Okinawa Trough - Ang Li; Nengyou Wu; Zhifeng Wan; Qing Li; Zhilei Sun; Feng Cai; Dong Feng (Marine and Petroleum Geology, 2024)

Early Cretaceous magmatism archives crustal architecture of northern Lhasa Terrane, central Tibetan Plateau - Wan-Li Tang; Feng Huang; Zheng-Wei Qin; Yun-Chuan Zeng; Ji-Feng Xu (Lithos, 2024)

Novel nanocomposites improve functional recovery of spinal cord injury by regulating NF-κB mediated microglia polarization - Huihui Sun; Yaqing Yang; Yaoyao Jin; Hao Chen; Aoying Li; Xizhao Chen; Junxiang Yin; Jun Cai; Liang Zhang; Xinmin Feng; Yongxiang Wang; Wu Xiong; et al. (Chemical Engineering Journal, 2024)

A dynamic modeling approach to predict water inflow during tunnel excavation in relatively uniform rock masses - Zhongxia Li; Jing Xiao; Junwei Wan; Jianmei Cheng; Haibo Feng; Hongbin Zhan; Shuai Yuan; Kun Huang (Tunnelling and Underground Space Technology, 2024)

Nitrogen addition does not alter symmetric responses of soil respiration to changing precipitation in a semi-arid grassland - Lingjie Kong; Jian Song; Jingyi Ru; Jiayin Feng; Jiawei Hou; Xueke Wang; Qingshan Zhang; Haidao Wang; Xiaojing Yue; Zhenxing Zhou; Dasheng Sun; Jiajia Zhang; et al. (Science of The Total Environment, 2024)

Two anachoropterid fern rachises from the in situ volcanic ash of the Whetstone Horizon (Kladno Formation, Pennsylvanian), Radnice Basin, Czech Republic - Wei-Ming Zhou; Josef Pšenička; Jana Votočková Frojdová; Jun Wang; Ming-Li Wan; Zhuo Feng (Palaeoworld, 2024)

Seasonal patterns, fate and ecological risk assessment of pharmaceutical compounds in a wastewater treatment plant with Bacillus bio-reactor treatment - Zi-Feng Zhang; Ying-Ying Fan; Xi-Mei Lu; Xi-ze Min; Wan-Li Ma; Li-Yan Liu; Yi-Fan Li; Wen-Long Li (Journal of Environmental Management, 2024)

Thermodynamic design and analysis of air-liquefied energy storage combined with LNG regasification system - Qingfeng Jiang; Shiqing Wan; Chongyao Pan; Guozeng Feng; Huaibing Li; Hansheng Feng; Bo Meng; Jiayang Gu; Yunchu Feng (International Journal of Refrigeration, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

FTO demethylates regulates cell-cycle progression by controlling CCND1 expression in luteinizing goat granulosa cells - Dongxu Li; Lei Zhou; Zifei Liu; Zhen Zhang; Weijia Mao; Wangwang Shi; Minghui Zhu; Feng Wang; Yongjie Wan (Theriogenology, 2024)

Microeukaryotes have unexpected importance in cold seep food webs through predation and parasitism - Longzhao Li; Feng Zhao; Sabine Filker; Weiyue Liu; Rongjie Zhao; Yuanyuan Wan; Kuidong Xu (Progress in Oceanography, 2024)

Potassium isotopes as a tracer of hydrothermal alteration in ore systems - Kun-Feng Qiu; Rolf L. Romer; Zheng-Yu Long; Hao-Cheng Yu; Simon Turner; Ruo-Qi Wan; Xiao-Qiang Li; Zi-Yue Gao; Jun Deng (Geochimica et Cosmochimica Acta, 2024)

Fungal community composition changes and reduced bacterial diversity drive improvements in the soil quality index during arable land restoration - Pingxing Wan; Zhongke Zhou; Ziqiang Yuan; Huihui Wei; Fuqiang Huang; Zhansheng Li; Feng-Min Li; Feng Zhang (Environmental Research, 2024)

Multicompartmented nanostructures with tunable interior complexities co-assembled by two plant proteins - Wenzhe Zhang; Ying Wan; Chaoyi Xue; Zhengxing Chen; Ren Wang; Wei Feng; Yanan Li; Tao Wang (Chemical Engineering Journal, 2024)

Therapeutic potential of dietary flavonoid hyperoside against non-communicable diseases: targeting underlying properties of diseases - Jia Xia; Yan Wan; Jiao-jiao Wu; Yu Yang; Jin-Feng Xu; Li Zhang; Dong Liu; Lu Chen; Fei Tang; Hui Ao; Cheng Peng (Critical Reviews in Food Science and Nutrition, 2024)

Occurrence, seasonal variation and gas/particle partitioning of current used pesticides (CUPs) across 60 °C temperature and 30° latitudes in China - Liang Wang; Gang Cao; Zi-Feng Zhang; Li-Yan Liu; Shi-Ming Jia; Meng-Qi Fu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

Plastic film mulching application improves potato yields, reduces ammonia emissions, but boosts the greenhouse gas emissions in China - Yalan Huang; Rongzhu Qin; Huihui Wei; Ning Chai; Yang Yang; Yuling Li; Pingxing Wan; Yufei Li; Wucheng Zhao; Siam Lawawirojwong; Tanita Suepa; Feng Zhang (Journal of Environmental Management, 2024)

Experimental research on the effect of water velocity on phosphorus release from sediments of a plateau cold water type river - Hang Wan; Yanan Huang; Xiaolong Cheng; Jingjie Feng; Ran Li (Journal of Contaminant Hydrology, 2024)

Associations between cold spells of different time types and coronary heart disease severity - Zhaoyuan Li; Jing Wan; Shouxin Peng; Ruonan Wang; Zhongli Dai; Cuiyi Liu; Yujia Feng; Hao Xiang (Environmental Pollution, 2024)

C-methylated homoisoflavanones from the rhizomes of polygonatum cyrtonema and their chemotaxonomic significance - Jiang Wan; Guangyao Mei; Jun-Xia Ma; Ze-Yu Zhao; Can Wang; Ziping Zhu; Junmin Li; Jin-Feng Hu (Biochemical Systematics and Ecology, 2024)

Functional characterization of genes related to triterpene and flavonoid biosynthesis in Cyclocarya paliurus - Shuang-yan Zhang; Yu-qing Peng; Gui-sheng Xiang; Wan-ling Song; Lei Feng; Xin-yue Jiang; Xue-jiao Li; Si-mei He; Sheng-chao Yang; Yan Zhao; Guang-hui Zhang (Planta, 2024)

LncRNA-mir3471-limd1 regulatory network plays critical roles in HIBD - Li Sun; Jun Wan; Bin Sun; Qiuyan Tian; Mei Li; Li-Xiao Xu; Chen-Xi Feng; Xiao Tong; Xing Feng; Xiaofeng Yang; Xin Ding (Experimental Brain Research, 2024)
The purpose of this study was to identify the target genes of tcon_00044595, elucidate its activation site, and provide novel insights into the pathogenesis and treatment of neonatal hypoxic–ischemic brain damage (HIBD). Through homologous blast analysis, we identified predicted target sequences in the neighboring regions of the long non-coding RNA (lncRNA) tcon_00044595, suggesting that limd1 is its target gene. Starbase was utilized to identify potential candidate microRNAs associated with the lncRNA. The interaction between the candidate microRNAs and limd1 was investigated and validated using various experimental methods including in vitro cell culture, cell transfection, dual fluorescence reporter detection system, and real-time PCR. Homology alignment analysis revealed that the lncRNA tcon_00044595 exhibited a 246 bp homologous sequence at the 3' end of the adjacent limd1 gene, with a conservation rate of 68%. Analysis conducted on Starbase online identified three potential microRNA candidates: miR-3471, miR-883a-5p, and miR-214-3p. Intracellular expression of the limd1 gene was significantly down-regulated upon transfection with miR-3471, while the other two microRNAs did not produce noticeable effects. Luciferase reporter assays identified two interaction sites (UTR-1, UTR-2) between miR-3471 and the limd1 3ʹUTR, with UTR-1 exhibiting a strong influence. Further CCK8 assay indicated a protective role of miR-3471 during low oxygen stroke in HIBD. The potential regulatory relationship between lncRNA (tcon_00044595), miR-3471, and the target gene limd1 suggests their involvement in the occurrence and development of HIBD, providing new insights for investigating the underlying mechanisms and exploring targeted therapeutic approaches for HIBD.

Exploring low-carbon mulching strategies for maize and wheat on-farm: Spatial responses, factors and mitigation potential - Huihui Wei; Kaiping Zhang; Ning Chai; Yue Wang; Yuling Li; Jianjun Yang; Matthew Tom Harrison; Ke Liu; Pingxing Wan; Wenjuan Zhang; Guojun Sun; Zhansheng Li; et al. (Science of The Total Environment, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Meroterpenoids with divers' rings systems from Phyllosticta capitalensis and their anti-inflammatory activity - Xiao-xia Zhu; Wan-qiu Liu; Zhao-xia Shi; Huang-yao Zhu; Si-qi Fan; Jie Zhang; Wen-yuan Liu; Li-Jun Xu; Qing-Jia Ren; Feng Feng; Jian Xu (Phytochemistry, 2024)

Diverse Late Triassic arc magmatism and porphyry Cu deposits in the southeastern Tibetan Plateau: Related to slab tear along a subducting passive margin? - Wan-Li Tang; Jian-Lin Chen; Tian-Nan Yang; An Yin; Ji-Feng Xu; Jiang-Bo Ren (Lithos, 2024)

TransCNNLoc: End-to-end pixel-level learning for 2D-to-3D pose estimation in dynamic indoor scenes - Shengjun Tang; Yusong Li; Jiawei Wan; You Li; Baoding Zhou; Renzhong Guo; Weixi Wang; Yuhong Feng (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Enhanced hydrophobic interaction between fish (Cyprinus carpio L.) scale gelatin and curcumin: Mechanism study - Haoxin Li; Wan Aida Wan Mustapha; Guilin Tian; Nan Dong; Feng Zhao; Xiaoping Zhang; Daoqi Long; Jia Liu (Food Chemistry, 2024)

Long-Life flexible mild Ag-Zn fibrous battery with bifunctional gel electrolyte - Yanzhe Zhu; Jiajun Fan; Shuo Zhang; Ziheng Feng; Chao Liu; Renbo Zhu; Yunjian Liu; Peiyuan Guan; Mengyao Li; Zhaojun Han; Tao Wan; Jianbo Tang; et al. (Chemical Engineering Journal, 2024)

Mechanically stable superhydrophobic coating of crosslinked polymer composite with self-healing ability - Xiao-Jing Guo; Meng-Chen Huang; Chao-Hua Xue; Hui-Di Wang; Zhong-Xue Bai; Yong-Gang Wu; Chao-Qun Ma; Zhong-Yang Shao; Zi-Hao Jiang; Li Wan; A-Jun Chang; Jing Li; et al. (Chemical Engineering Journal, 2024)

Rosmarinic acid against cognitive impairment via RACK1/HIF-1α regulated microglial polarization in sepsis-surviving mice - Dan-yang Liu; Yao Wu; Zi-qi Feng; Yang Yu; Hua-wei Cai; Shi-ping Liao; Tao Zeng; Ling Zhu; Xia Wang; Li-hong Wan (Chemico-Biological Interactions, 2024)

Seismic response of a mid-story isolated structure considering SSI in mountainous areas under long-period earthquakes - Feng Wan; Shengwu Qin; Dewen Liu; Tiange Zhao; Yanping Zheng; Hang Shan; Zhiang Li; Fusong Peng; Jingran Xu; Min Lei (Earthquake Engineering and Engineering Vibration, 2024)

Controlled-diffusion centrifugal microfluidic for rapid antibiotic susceptibility testing - Zheng Pang; Shunji Li; Shangang Wang; Zonglin Cai; Shuo Zhang; Chao Wan; Jieqing Wang; Yiwei Li; Peng Chen; Bi-Feng Liu (Analytica Chimica Acta, 2024)

Cross-regional scale studies of organochlorine pesticides in air in China: Pollution characteristic, seasonal variation, and gas/particle partitioning - Liang Wang; Gang Cao; Li-Yan Liu; Zi-Feng Zhang; Shi-Ming Jia; Meng-Qi Fu; Wan-Li Ma (Science of The Total Environment, 2023)

Adipocyte-derived exosomes promote the progression of triple-negative breast cancer through circCRIM1-dependent OGA activation - Yuehua Li; Baohong Jiang; Lijun Zeng; Yuanbin Tang; Xiaowen Qi; Zhixing Wan; Wenjie Feng; Liming Xie; Rongfang He; Hongbo Zhu; Yimou Wu (Environmental Research, 2023)

Modified DNDC model to improve performance of soil temperature simulation under plastic film mulching and snow cover - Wucheng Zhao; Xuetong Zhang; Shasha Zhang; Ningning Zhang; Pingxing Wan; Yufei Li; Kaiping Zhang; Zeyu Zhao; Yue Wang; Zhixin Li; Jianjun Yang; Zhansheng Li; et al. (Computers and Electronics in Agriculture, 2023)

Three-dimensional hydrophobic melamine@methyl trichlorosilane/polydimethylsiloxane sponge for consecutive and long-term oil/water separation - Wubo Wan; Zhuang Yang; Tao Tan; Yu Li; Zehao Zhang; Peng Zhang; Feng He (Chemical Engineering Journal, 2023)

Insights into simultaneous adsorption of orthophosphate (PO43−) and 1-hydroxyethane 1,1-diphosphonic acid (HEDP) by kaolin/lanthanum carbonate composites: Experimental analysis and DFT calculations - Jun Wan; Rui Li; Xiaonan Feng; Jiazhi Yang; Yuxuan Ye; Sifeng Jian; Xiaowei Zhang (Chemical Engineering Journal, 2023)

Molybdenum isotope heterogeneity of metal sulfides from magmatic hydrothermal systems - Wan-li Tang; Ji-feng Xu; Kang Cao; Jie Li; Jian-lin Chen (Chemical Geology, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

Acid-induced tubular g-C3N4 for the selective generation of singlet oxygen by energy transfer: Implications for the photocatalytic degradation of parabens in real water environments - Yu-Wei Li; Shu-Zhi Li; Min-bo Zhao; Li-Yan Liu; Zi-Feng Zhang; Wan-Li Ma (Science of The Total Environment, 2023)

Insight into the effect of a heavy metal mixture on neurological damage in rats through combined serum metabolomic and brain proteomic analyses - Jie Xie; Fankun Zhou; Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Shuo Yang; Jiajun Li; Xin Wan; Lingyu Yan; Peishan Liu; Hui Cheng; et al. (Science of The Total Environment, 2023)

Neoproterozoic tectonic transition from subduction to back-arc extension along the western Yangtze Block, South China: Petrological evidence of Nb-enriched basalts and arc-type intrusive rocks - Yu Zhu; Shao-cong Lai; Wan-li Xie; Jiang-feng Qin; Ren-zhi Zhu; Shao-wei Zhao; Min Liu; Fang-yi Zhang; Ze-zhong Zhang; Hang Yang (Gondwana Research, 2023)

Formation and isomerization of (Z)-methyl epijasmonate, the key contributor of the orchid-like aroma, during tea processing - Zhihui Feng; Yifan Li; Ping Zhang; Jieqiong Wang; Yongquan Xu; Yingying Feng; Xiaoting Zhai; Xiaogen Yang; Xiaochun Wan; Junfeng Yin (Food Research International, 2023)

Effects of selenium (Se) uptake on plant growth and yield in common buckwheat (Fagopyrum esculentum Moench) - Jincai Tao; Jiajun Leng; Xinhui Lei; Chenxi Wan; Deli Li; Yixin Wu; Qinghua Yang; Pengke Wang; Baili Feng; Jinfeng Gao (Field Crops Research, 2023)

Zero-energy consuming fast decomposition of H2O2 over mullite oxide YMn2O5 - Shen Zhang; Ao Zhu; Xiang Wan; Meng Yu; Daqing Sun; Zhenguo Li; Guoliang Shi; Yinchang Feng; Jiaguo Yan; Chunning Zhao; Weichao Wang (Chemical Engineering Journal, 2023)

Designing multifunctional silica coatings for enhanced broadband antireflection and microfiber contamination sensing - Xinshu Zou; Guorui Zhou; Yi Wan; Bo Li; Bo Jiang; Hongwei Yan; Feng Wang (Chemical Engineering Journal, 2023)

Coordination effect enhanced visualization of latent fingerprint with Eu (TTA)3phen-SiO2 microspheres - Kang Zhang; Meng-Jiao Zhu; Yi-Wen Zhou; Xiao Liu; Feng Chen; Yu-Yang Zhou; Wan-Fei Li; Sheng Liu; Yun Jiang; Shou-Qing Liu (Analytica Chimica Acta, 2023)

TIPS: A three-dimensional phenotypic measurement system for individual maize tassel based on TreeQSM - Bo Xu; Xiangyuan Wan; Hao Yang; Haikuan Feng; Yuanyuan Fu; Haiyan Cen; Binbin Wang; Zhoufeng Zhang; Siyuan Li; Chunjiang Zhao; Guijun Yang (Computers and Electronics in Agriculture, 2023)

Inoculation of Escherichia coli enriched the key functional bacteria that intensified cadmium accumulation by halophyte Suaeda salsa in saline soils - Tao He; Zhi-Min Xu; Jun-Feng Wang; Ke Zhang; Fo-Peng Wang; Wan-Li Li; Ping Tian; Qu-Sheng Li (Journal of Hazardous Materials, 2023)

Effects of nitrogen addition and changing precipitation on soil heterotrophic respiration in a climate transitional forest - Jiayin Feng; Dianjie Wang; Jingjing Gao; Yuanfeng Hao; Zheng Li; Tiantian Wang; Shiqiang Wan (Plant and Soil, 2023)

A novel electrochemical aptasensor based on eco-friendly synthesized titanium dioxide nanosheets and polyethyleneimine grafted reduced graphene oxide for ultrasensitive and selective detection of ciprofloxacin - Yangguang Zhu; Xiufen Li; Mengfan Wu; Mingjiao Shi; Qichen Tian; Li Fu; Hsu-Sheng Tsai; Wan-Feng Xie; Guosong Lai; Gang Wang; Nan Jiang; Chen Ye; et al. (Analytica Chimica Acta, 2023)

Association between multiple metal(loid)s exposure and renal function: a cross-sectional study from southeastern China - Guihua Du; Xiaoguang Song; Fankun Zhou; Lu Ouyang; Qi Li; Shiying Ruan; Shuo Yang; Shaoqi Rao; Xin Wan; Jie Xie; Chang Feng; Guangqin Fan (Environmental Science and Pollution Research, 2023)

Peganutonin A, a novel melatonin analogue from the seeds of Peganum harmala - Jian-Bo Liu; Wan-Ying Li; Xue Zhao; Feng-Ying Yang; Lei Fang (Phytochemistry Letters, 2023)

Effectively removing gaseous polycyclic aromatic hydrocarbons (PAHs) by willow catkins: Do you still dislike the catkins floating? - Peng-Tuan Hu; Dong-Hai Liu; Zhi-Guo Cao; Hong Wei; Fu-Jie Zhu; Wan-Li Ma; Zi-Feng Zhang; Li-Yan Liu; Jing-Lan Feng; Yong-Feng Li; Yu-Fei Li; Yi-Fan Li (Journal of Hazardous Materials, 2023)

Depletion attraction driven formation of Spirulina emulsion gels for 3D printing - Guangxin Feng; Gaoshang Wang; Qing Li; Chuanwu Han; Dong Wei; Jian Guo; Zhili Wan; Jinmei Wang; Xiaoquan Yang (Food Hydrocolloids, 2023)

An online intelligent management method for wastewater treatment supported by coupling data-driven and mechanism models - Jian-Hui Wang; Du-Jiang Zhao; Wan-Shan Liao; Mohamed S. Mahmoud; Zhi-Wei Guo; Hui-Min Li; Xu Gao; Dong Feng; Long-Fei Shi; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2023)

Enhanced viability of probiotics encapsulated within synthetic/natural biopolymers by the addition of gum arabic via electrohydrodynamic processing - Jiage Ma; Tianzhu Li; Qingyun Wang; Cong Xu; Wei Yu; Hongliang Yu; Wan Wang; Zhibiao Feng; Lijun Chen; Juncai Hou; Zhanmei Jiang (Food Chemistry, 2023)

Axially chiral thermally activated delayed fluorescence emitters enabled by molecular engineering towards high-performance circularly polarized OLEDs - Shi-Peng Wan; Wen-Long Zhao; Ke-Ke Tan; Hai-Yan Lu; Meng Li; Chuan-Feng Chen (Chemical Engineering Journal, 2023)

Spatial distribution and temporal trend of organochlorine pesticides in Chinese surface soil - Shuai Hao; Wen-Long Li; Li-Yan Liu; Zi-Feng Zhang; Wan-Li Ma; Yi-Fan Li (Environmental Science and Pollution Research, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Removal of antibiotic resistant bacteria and genes by nanoscale zero-valent iron activated persulfate: Implication for the contribution of pH decrease - Chun-shuang Zhou; Guang-li Cao; Xiu-Kun Wu; Bing-feng Liu; Qing-Yue Qi; Wan-Li Ma (Journal of Hazardous Materials, 2023)

Precisely mapping a major QTL for grain weight on chromosome 5B of the founder parent Chuanmai42 in the wheat-growing region of southwestern China - Meijin Ye; Hongshen Wan; Wuyun Yang; Zehou Liu; Qin Wang; Ning Yang; Hai Long; Guangbing Deng; Yumin Yang; Hong Feng; Yonghong Zhou; Cairong Yang; et al. (Theoretical and Applied Genetics, 2023)

Another Year of Record Heat for the Oceans - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Fujiang Yu; et al. (Advances in Atmospheric Sciences, 2023)
Changes in ocean heat content (OHC), salinity, and stratification provide critical indicators for changes in Earth’s energy and water cycles. These cycles have been profoundly altered due to the emission of greenhouse gasses and other anthropogenic substances by human activities, driving pervasive changes in Earth’s climate system. In 2022, the world’s oceans, as given by OHC, were again the hottest in the historical record and exceeded the previous 2021 record maximum. According to IAP/CAS data, the 0–2000 m OHC in 2022 exceeded that of 2021 by 10.9 ± 8.3 ZJ (1 Zetta Joules = 10 21 Joules); and according to NCEI/NOAA data, by 9.1 ± 8.7 ZJ. Among seven regions, four basins (the North Pacific, North Atlantic, the Mediterranean Sea, and southern oceans) recorded their highest OHC since the 1950s. The salinity-contrast index, a quantification of the “salty gets saltier—fresh gets fresher” pattern, also reached its highest level on record in 2022, implying continued amplification of the global hydrological cycle. Regional OHC and salinity changes in 2022 were dominated by a strong La Niña event. Global upper-ocean stratification continued its increasing trend and was among the top seven in 2022.

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

Long-acting removal of high-toxic p-nitrophenol in wastewater via peroxymonosulfate activation by cyclic membrane catalysis - Jingxin Yang; Yongshi Huang; Yuhang Cheng; Xueyan Wu; Jiangyan Lu; Qingnan Wan; Jianxian Feng; Qingyi Zeng; Shuaifei Zhao; Li Yu; Zhu Xiong (Journal of Cleaner Production, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

Implications of steep hilly terrain for modeling wind-turbine wakes - Ding Wang; Dachuan Feng; Huaiwu Peng; Feng Mao; Mohammad Hossein Doranehgard; Vikrant Gupta; Larry K.B. Li; Minping Wan (Journal of Cleaner Production, 2023)

Association of occupational exposure to polycyclic aromatic hydrocarbons in workers with hypertension from a northeastern Chinese petrochemical industrial area - Yu Sun; Ze Kan; Zi-Feng Zhang; Li Song; Chao Jiang; Ji Wang; Wan-Li Ma; Yi-Fan Li; Li Wang; Li-Yan Liu (Environmental Pollution, 2023)

Soil warming decreases carbon availability and reduces metabolic functions of bacteria - Pingxing Wan; Feng Zhang; Kaiping Zhang; Yufei Li; Rongzhu Qin; Jianjun Yang; Chao Fang; Yakov Kuzyakov; Shiqing Li; Feng-Min Li (CATENA, 2023)

Reclamation of heavy coastal silt saline soil and optimal tomato production through a drip irrigation system with saline water - Di Feng; Chitao Sun; Xiaobin Li; Xiaoan Sun; Shuqin Wan; Caixia Li; Songrui Ning (Plant and Soil, 2023)

Bioleaching and immobilizing of copper and zinc using endophytes coupled with biochar-hydroxyapatite: Bipolar remediation for heavy metals contaminated mining soils - Weiran Feng; Xiao Xiao; Junjie Li; Qicheng Xiao; Li Ma; Qifeng Gao; Yuke Wan; Yutian Huang; Ting Liu; Xubiao Luo; Shenglian Luo; Guisheng Zeng; et al. (Chemosphere, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Reducing plant pathogens could increase crop yields after plastic film mulching - Pingxing Wan; Ningning Zhang; Yufei Li; Shiqing Li; Feng-Min Li; Zengtuan Cui; Feng Zhang (Science of The Total Environment, 2023)

National-scale monitoring of historic used organochlorine pesticides (OCPs) and current used pesticides (CUPs) in Chinese surface soil: Old topic and new story - Liang Wang; Zi-Feng Zhang; Li-Yan Liu; Fu-Jie Zhu; Wan-Li Ma (Journal of Hazardous Materials, 2023)

Size-resolved environmentally persistent free radicals in cold region atmosphere: Implications for inhalation exposure risk - Shi-Ming Jia; De-Qi Wang; Li-Yan Liu; Zi-Feng Zhang; Wan-Li Ma (Journal of Hazardous Materials, 2023)

Flexural behavior of steel-MPC based high performance concrete composite beams subjected to hogging moments - Jing Zhang; Tao Li; Xiamin Hu; Shuhong Gong; Wan Hong; Jianmin Feng (Engineering Structures, 2023)

Absence of water content contrast between lithosphere and asthenosphere in subduction zone - Yuto Sato; Eiichi Takahashi; Chang-Ming Xing; Li Li; Ze-Xian Cui; Wan-Feng Zhang; Xiao-Ping Xia (Earth and Planetary Science Letters, 2023)

Industrial scale thin-film composite membrane modules for salinity-gradient energy harvesting through pressure retarded osmosis - Jiun Hui Low; Junyou Zhang; Weikun Paul Li; Tianshi Yang; Chun Feng Wan; Farhana Esa; Marn Soon Qua; Karikalan Mottaiyan; Suresh Murugan; Muhammad Aiman; Adil Dhalla; Tai-Shung Chung; et al. (Desalination, 2023)

Seismic Multiple Attenuation in the Continent–Ocean Transition Zone of the Northern South China Sea - Nan Chen; Chun-Feng Li; Yong-Lin Wen; Peng Wang; Xiu-Lian Zhao; Xiao-Li Wan (Journal of Marine Science and Engineering, 2023)
In this study, we process four new multichannel reflection seismic profiles acquired in 2015 and 2016 in the continent–ocean transition zone (COT) of the northern South China Sea (SCS). We apply a multi-domain, progressive, and seabed-controlled denoising technique and obtain a good denoising effect. Combining velocity analysis in the multi-round time domain and forward modeling, we analyze the types and characteristics of multiples in the study area and formulate an effective demultiple technique to attenuate strong seabed multiples, diffracted multiples from rough seafloor, and other multiples from deep reflectors. The processing results show that the sea surface-related multiple elimination technique predicts the sea surface-related multiples accurately by data convolution, and has a good effect in attenuating seabed multiples. Diffracted multiple attenuation method extracts high-frequency and high-energy diffracted multiples, and suppresses multiples by the energy ratios of multiples to primary events. To attenuate deep multiples, we select predictive deconvolution to attenuate periodic deep multiples after many trials and detailed analysis. The combination of these different techniques in sequence proves to be quite effective in attenuating different seismic multiples in the COT. The imaged crustal structures near the COT often show strong magmatism and/or basement uplifting. The faulted and thinned continental crust adjacent to the COT corresponds to the lowest free-air gravity anomalies. Gravity anomalies often increase from the COT to the oceanic crust. An exception is to the northeast of the SCS, where the relatively wide COT shows very high gravity anomalies, likely induced by mantle upwelling and serpentinization.

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Solar-induced efficient propylparaben photodegradation by nitrogen vacancy engineered reticulate g-C3N4: Morphology, activity and mechanism - Yu-Wei Li; Zi-Feng Zhang; Shu-Zhi Li; Li-Yan Liu; Wan-Li Ma (Science of The Total Environment, 2023)

Phylogeny, character evolution, and biogeography of the fern genus Bolbitis (Dryopteridaceae) - Li-Yun Nie; Liang Zhang; Zhen-Long Liang; Rossarin Pollawatn; Yue-Hong Yan; Ngan Thi Lu; Ralf Knapp; Xia Wan; Daniele Cicuzza; Xin-Xin Cheng; Hong-Feng Chen; Ai-Hua Wang; et al. (Molecular Phylogenetics and Evolution, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Nickel and oxygen-containing functional groups co-decorated graphene-like shells as catalytic sites with excellent selective hydrogenation activity and robust stability - Wei Yan; FaZhan Xiao; Xin Li; Wei He; YongYue Yao; DongChuang Wan; Xin Liu; Yi Liu; Feng Feng; Qunfeng Zhang; Chunshan Lu; Xiaonian Li (Chemical Engineering Journal, 2023)

Effect of divalent cations on electrochemiluminescence of metal-organic frameworks in bioassay - Xuyu Feng; Bin Li; Longyi Zhu; Wen Chen; Ying Wu; Yanru Duan; Meiyan Song; Ying Wan; Shengyuan Deng (Analytica Chimica Acta, 2023)

Transcriptome‐based analyses of adaptive divergence between two closely related spruce species on the Qinghai–Tibet plateau and adjacent regions - Shuo Feng; Wei Wan; Yang Li; DongLei Wang; Guangpeng Ren; Tao Ma; Dafu Ru (Molecular Ecology, 2023)
Speciation among populations connected by gene flow is driven by adaptation to different environments, but underlying gene–environment associations remain largely unknown. Here, 162 individuals from 32 populations were sampled to obtain 191,648 independent single nucleotide polymorphisms (SNPs) across the genomes of two closely related spruce species, Picea asperata and Picea crassifolia , which occur on the Qinghai–Tibet Plateau and in surrounding regions. Using the SNP data set, genotype–environment associations and demographic modelling were used to examine local adaptation and genetic divergence between these two species. While morphologically similar, the two Picea species were genetically differentiated in multiple analyses. These species diverged despite continuous gene flow, and their initial divergence was dated back to the late Quaternary. The effective population sizes of both species have expanded since their divergence, as confirmed by niche distribution simulations. A total of 6365 genes were associated with the tested environmental variables; of these, 41 were positively selected in P. asperata and were mainly associated with temperature, while 83 were positively selected in P. crassifolia and were primarily associated with precipitation. These results deepen our understanding of the adaptive divergence and demographic histories of these two spruce species and highlight the importance of genomic data in deciphering the environmental selection underlying Quaternary interspecific divergence.

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

CircCERS6 Suppresses the Development of Epithelial Ovarian Cancer Through Mediating miR-630/RASSF8 - Xiaoqin Li; Xuemei Jiang; Jing Lu; Yuting Lin; Lan Jiang; Yan Li; Feng Wan; Changmin Wang (Biochemical Genetics, 2022)

New taxonomic framework for Arthrodermataceae: a comprehensive analysis based on their phylogenetic reconstruction, divergence time estimation, phylogenetic split network, and phylogeography - Zhi-Yuan Zhang; Yu-Lian Ren; Xin Li; Wan-Hao Chen; Jian-Dong Liang; Yan-Feng Han; Zong-Qi Liang (Antonie van Leeuwenhoek, 2022)

Age-Related miRNA-Mediated Regulatory Networks Orchestrating Chronological Development of Meristems in Larix Kaempferi - Wan-Feng Li; Li-Wang Qi; Wen-Hua Yang (Journal of Plant Growth Regulation, 2022)
Plant growth and development is usually characterized by chronological age over the plants’ lifetimes. Age-related changes actually originate with meristems because they control if, where, when, and how new tissues are formed along the axis of the shoot. The “time-keeping” of plant meristem development is a complex process. To uncover the post-transcriptional regulation underlying the chronological development of Larix kaempferi (Japanese larch) meristems, we investigated the miRNA-mediated regulatory network in the defoliated, uppermost main stems of 1-, 2-, 5-, 10-, 25-, and 50-year-old L. kaempferi using RNA-seq methods. We identified 29 high-confidence miRNAs, three of which were defined, age-related miRNAs whose expression changed depending on L. kaempferi age, and 17 showed coordinated expression patterns with three age-related miRNAs based on hierarchical correlations. All hierarchically coordinated miRNAs and their targets constituted a miRNA-mediated regulatory network. The developmental timing pathway lka-miR-1-5p-156- SBP / SPL ( Squamosa Promoter Binding Protein-Like ), the lignin biosynthesis pathway lka-miR-7,13-5p-397- LAC ( Laccase ), and an unknown pathway lka-miR-3-5p- CMSS1 ( Cms1 Ribosomal Small Subunit Homolog ) were age-driven, and information from auxin and light could be integrated by the lka-miR-9-5p-390- TAS / ARF ( Trans-Acting siRNA3 /Auxin Response Factor) and lka-miR-8-5p- IRL4 (Plant Intracellular Ras-Group-Related LRR Protein 4 ) pathways, respectively. Age-driven regulatory network will lead the way to understand which and how genes mutually cross-regulate their activity orchestrating development of meristems of L. kaempferi with age. We also discussed and contributed to miRNA annotation and nomenclature.

Dynamic response of the inhomogeneous pavement structure containing a buried fault zone under the moving aircraft loads - Jiawei Wan; Bin Li; Yang Gao; Chengxuan Tan; Chengjun Feng; Peng Zhang (Bulletin of Engineering Geology and the Environment, 2022)

Association between meteorological factors and hospital admissions for uveitis in Hefei, China: a time-series study - Fan Cao; Yi-Sheng He; Kun Xiang; Cheng-Huan Wan; Wei Liu; Yan-Chao Gui; Hai-Feng Pan; Zheng-Xuan Jiang; Li-Ming Tao (Environmental Science and Pollution Research, 2022)

Geochemical characteristics and growth suitability assessment of Scutellaria baicalensis Georgi in the Earth’s critical zone of North China - Xia Li; Xiao-feng Wei; Jin Wu; Zhi-qiang Yin; Li-qin Wan; Hou-yun Sun; Yong-long An (Journal of Mountain Science, 2022)

Streptomyces griseicoloratus sp. nov., isolated from soil in cotton fields in Xinjiang, China - Li Xing; Ying-ying Xia; Qiao-Yan Zhang; Zhan-Feng Xia; Chuan-xing Wan; Li-li Zhang; Xiao-Xia Luo (Archives of Microbiology, 2022)

Effects of dihydroartemisinin, a metabolite of artemisinin, on colon cancer chemoprevention and adaptive immune regulation - Chong-Zhi Wang; Chunping Wan; Yun Luo; Chun-Feng Zhang; Qi-Hui Zhang; Lina Chen; Zhi Liu; Daniel H. Wang; Mallory Lager; Cang-Hai Li; Ting-Liang Jiang; Lifei Hou; et al. (Molecular Biology Reports, 2022)

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

Expression pattern of alkB homolog 5 in goat testis and its role in spermatogonial stem cells - Zifei Liu; Yu Cai; Mingtian Deng; Dongxu Li; Qingqing Leng; Liangyue Shi; Yutong Tang; Feng Wang; Yongjie Wan (Cell and Tissue Research, 2022)

Evolutionary characteristics and phylogeny of cotton chloroplast tRNAs - Ning Wang; Wan-Lin Dong; Xiao-Jing Zhang; Tong Zhou; Xiao-Juan Huang; Bao-Guo Li; Jian-Ni Liu; Xiong-Feng Ma; Zhong-Hu Li (Planta, 2021)

The Decision Strategies of Adolescents with Different Emotional Stabilities in Unfair Situations - Yajing Si; Lin Jiang; Chanlin Yi; Qi Zhang; Cunbo Li; Jing Yu; Peiyang Li; Qiang Liu; Feng Wan; Fali Li; Dezhong Yao; Peng Xu (Neuroscience Bulletin, 2021)

Nitrogen fertilizer management affects remobilization of the immobilized cadmium in soil and its accumulation in crop tissues - Jun-Feng Wang; Wan-Li Li; Qu-Sheng Li; Li-Li Wang; Tao He; Fo-Peng Wang; Zhi-Min Xu (Environmental Science and Pollution Research, 2021)

miR-34c inhibits PDGF-BB-induced HAVSMCs phenotypic transformation and proliferation via PDGFR-β/SIRT1 pathway - Wei-feng Wan; Xin Zhang; Chang-ren Huang; Li-gang Chen; Xiao-bo Yang; Kun-yang Bao; Tang-ming Peng (Molecular Biology Reports, 2021)
The purpose of this study was to explore the effect of miR-34c on PDGF-BB-induced HAVSMCs phenotypic transformation and proliferation via PDGFR-β/SIRT1 pathway, so as to find a new method for early diagnosis and treatment of cardiovascular disease. HA-VSMCs were treated with platelet-derived growth factor-BB (PDGF-BB) at 0 h, 12 h, 24 h, 48 h or 36 h to explore the optimal time for phenotypic transformation of VSMCs. And then, PDGF-BB-induced HA-VSMCs were transfected with miR-34c mimics/mimics NC and pcDNA3.1-PDGFR-β/pcDNA3.1-NC to observe cell biological behaviour. CCK8 was used to detect cell proliferation activity. Transwell chamber assay was used to detect cell invasion. Early apoptosis was analyzed by flow cytometry. The expression of α-SMA and Smemb was detected by immunofluorescence staining. The expressions of PDGFR-β, IRF9, Acetyl-NF-κB/p65, Acetyl-p53 and CyclinD1 were analyzed by Western blot analysis. The expression of miR-34a, miR-34b and miR-34c was detected by RT-PCR, and the targeting relationship between miR-34c and PDGFR-β was detected by luciferase reporting assay. The results indicated the proliferation and migration of PDGF-BB-induced HA-VSMCs significantly increased, and apoptosis significantly decreased. Besides, α-SMA decreased significantly, while Smemb increased significantly. Furthermore, expressions of PDGFR-β, IRF9, Acetyl-NF-κB/p65, Acetyl-p53 and CyclinD1 increased significantly, and SIRT1 decreased significantly. Experimental results showed that, miR-34c mimics significantly inhibited cell proliferation and migration, and promoted cell apoptosis, and miR-34c inhibitor had the opposite effects. MiR-34c mimics significantly increased α-SMA expression and decreased Smemb expression, while the opposite effects were reflected after transfection with miR-34c inhibitor. Moreover, miR-34c mimics significantly decreased the expressions of PDGFR-β, IRF9, Acetyl-NF-κB/p65, Acetyl-p53 and CyclinD1, and significantly increased the expression of SIRT1, while miR-34c inhibitor had the opposite effects. Luciferase assay confirmed that PDGFR-β was a potential target of miR-34c. Subsequently, PDGF-BB-induced HA-VSMCs were co-transfected with miR-34c mimics and pcDNA3.1-PDGFR-β. The results indicated that PDGFR-β reversed the biological function of miR-34c mimic. The results revealed the potential application value of miR-34c as a marker molecule of phenotypic transformation, providing a potential target for improving phenotypic transformation.

Transcriptional and post-transcriptional regulation of the miR171-LaSCL6 module during somatic embryogenesis in Larix kaempferi - Qiao-Lu Zang; Yao Zhang; Su-Ying Han; Wan-Feng Li; Li-Wang Qi (Trees, 2021)
Key message Expression analysis of Larix kaempferi mature miR171s and their primary transcripts and target gene LaSCL6 during somatic embryogenesis revealed the transcriptional and post-transcriptional regulation of the miR171- LaSCL6 module. Abstract Somatic embryogenesis provides a useful experimental system for studying the regulatory mechanisms of plant development. The level and activity of microRNA171 (miR171) fluctuate during somatic embryogenesis in Larix kaempferi , but the underlying mechanisms are still unclear. Here, in L. kaempferi we identified five members of the miR171 family, which cleave LaSCL6 mRNA at different sites. In addition, we improved the method of measuring miRNA activity in a more direct way. Furthermore, we measured the expression patterns of mature miR171s and their primary transcripts during somatic embryogenesis in L. kaempferi and found that their patterns differed, indicating that the transcription of MIR171 genes and the subsequent cleavage of their intermediate products are regulated. Taken together, our findings not only offer a means to study the regulation of miRNA activity, but also provide further insight into the regulation of L . kaempferi somatic embryogenesis by miR171- LaSCL6 .

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

New geochronological and geochemical data of the Longsheng mafic-ultramafic suite in northern Guangxi, China, and their implications in Rodinia breakup - Yizhi Liu; Ya Qin; Zuohai Feng; Saisai Li; Lei Wan; Chunzeng Wang (Arabian Journal of Geosciences, 2021)

LncRNA TUG1 promotes esophageal cancer development through regulating PLK1 expression by sponging miR-1294 - Mingzhu Zong; Wanting Feng; Li Wan; Xiaojuan Yu; Weiyong Yu (Biotechnology Letters, 2020)

Prediction and Identification of Epitopes in the Emy162 Antigen of Echinococcus multilocularis - Ming-Quan Pang; Feng Tang; Hai-Jiu Wang; Ying Zhou; Li Ren; Run-Le Li; Hu Zhou; Chen-Fei Wan; Chuan-Chuan Liu; Cai-Rang Yangdan; Hai-Ning Fan (Acta Parasitologica, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Overexpression of PREX1 in oral squamous cell carcinoma indicates poor prognosis - Shu-Cheng Wan; Hao Wu; Hao Li; Wei-Wei Deng; Yao Xiao; Cong-Cong Wu; Lei-Lei Yang; Wen-Feng Zhang; Zhi-Jun Sun (Journal of Molecular Histology, 2020)

Occurrence and partitioning of brominated flame retardants (BFRs) in indoor air and dust: a 15-month case study in a test home - Jia-Qi Guo; Yong-feng Li; Li-Yan Liu; Chun-Yan Huo; Yu Sun; Wan-li Ma; Zi-feng Zhang; Yi-Fan Li (Environmental Science and Pollution Research, 2020)

Responses of late embryogenesis-abundant genes in Leymus chinensis to water deficit - Dongli Wan; Xiu Feng; Yongqing Wan; Yong Ding; Heping Li (Brazilian Journal of Botany, 2020)

Genesis of the Linghu Au deposit in Xiaoqinling Region, Henan province, China: Constraints from fluid inclusions and isotope systematics - Wei Zeng; Zhi-gao Wang; Duo Wan; Feng-yue Sun; Cheng-dong Li; Reng-an Yu; Jia-ying Wang; Jian-chang Xu (Arabian Journal of Geosciences, 2020)

Characteristics and main causes of earth fissures in northeastern Beijing Plain, China - Jiawei Wan; Bin Li; Chengxuan Tan; Chengjun Feng; Peng Zhang; Bangshen Qi (Bulletin of Engineering Geology and the Environment, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

A novel hydrogel for highly efficient adsorption of Cu(II): synthesis, characterization, and mechanisms - Jun Wan; Lin Chen; Qiang Li; Yuxuan Ye; Xiaonan Feng; Aijiao Zhou; Xuejun Long; Dongsheng Xia; Tian C. Zhang (Environmental Science and Pollution Research, 2020)

The Family of Peanut Fatty Acid Desaturase Genes and a Functional Analysis of Four ω-3 AhFAD3 Members - Zhenying Peng; Jian Ruan; Haiying Tian; Lei Shan; Jingjing Meng; Feng Guo; Zhimeng Zhang; Hong Ding; Shubo Wan; Xinguo Li (Plant Molecular Biology Reporter, 2020)
The synthesis of α-linolenic acid (ALA) requires the activity of ω-3 fatty acid desaturases (ω-3 FADs). The quality of peanut oil would be much improved if the content of ALA could be increased. A scan of the peanut genome revealed that it harbored 36 FAD genes, mapping to 16 of the species’ 20 chromosomes. A phylogenetic analysis concluded that these genes belonged to six sub-families, namely stearoyl-acyl-acyl carrier protein desaturases ( SAD ), FAD2 , FAD3 , FAD4/5 , FAD6 and FAD7/8 . Of these, FAD3 and FAD7/8 encoded ω-3 FADs, while genes belonging to the other four sub-families encoded ω-6 FADs. Based on RNA-Seq data, each of the 36 FAD genes was shown to be transcribed in non-stressed plants, but there was variation between them with respect to which organs they were transcribed in. Four ω-3 AhFAD3 genes were functionally characterized; when expressed in Arabidopsis thaliana protoplasts, each was localized mainly in the endoplasmic reticulum, while within peanut, the genes were more strongly transcribed in the developing seed than in either the root or the leaf. When constitutively expressed in Arabidopsis thaliana , both the total fatty acid content of the seed and the relative contribution of ALA were increased. The transgenic seedlings also exhibited an improved level of survival when challenged by salinity stress.

Genome-Wide Analysis of LAZ1 Gene Family from Maize - Bing Liang Liu; Hao Qiang Yu; Qian Wen; Feng Ling Fu; Wan Chen Li (Journal of Plant Growth Regulation, 2020)

Hydrogeochemical and isotopic characteristics of surface water and groundwater in the Qinghai Lake catchment (China) - Sihai Liang; Juan Guo; Pan Wu; Yuqing Feng; Xusheng Wang; Guangjun Wang; Weilin Xu; Yinfei Luo; Li Wan (Arabian Journal of Geosciences, 2020)

Comparison between two kinds of natural pollen traps in tropical China: ants’ nests on tree branches versus surface soil - Zhi-Yong Zhang; Feng-Chun Yang; Dong-Mei Cheng; David K. Ferguson; Wan Hu; Yue-Zhuo Li; Cheng-Sen Li (Palynology, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Transcriptome-wide analysis to dissect the transcription factors orchestrating the phase change from vegetative to reproductive development in Larix kaempferi - Wei-Bo Xiang; Wan-Feng Li; Shou-Gong Zhang; Li-Wang Qi (Tree Genetics & Genomes, 2019)

Exploring the Potential of Mesoporous Silica as a Carrier for Puerarin: Characterization, Physical Stability, and In Vivo Pharmacokinetics - Zhi Wang; Bei-Ni Ye; Yong-Tai Zhang; Jian-Xu Xie; Wan-Si Li; Hong-Tao Zhang; Ying Liu; Nian-Ping Feng (AAPS PharmSciTech, 2019)

Regulation of LaSCL6 expression by genomic structure, alternative splicing, and microRNA in Larix kaempferi - Qiao-Lu Zang; Wan-Feng Li; Li-Wang Qi (Tree Genetics & Genomes, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Adsorption and sequestration of cadmium ions by polyptychial mesoporous biochar derived from Bacillus sp. biomass - Feng Li; Yixin Tang; Chengcheng Li; Yang Zheng; Xingwang Liu; Chuang Feng; Wan Zhao; Fang Wang (Environmental Science and Pollution Research, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

Vegetation phenology and its variations in the Tibetan Plateau, China - Sihai Liang; Canbin Lv; Guangjun Wang; Yuqing Feng; Qingbai Wu; Li Wan; Yuanqing Tong (International Journal of Remote Sensing, 2019)

Dietary Iron Modulates Glucose and Lipid Homeostasis in Diabetic Mice - Wan Ma; Yunfei Feng; Li Jia; Shuhui Li; Jiahui Li; Zhenjie Wang; Xiaoyun Chen; Huahua Du (Biological Trace Element Research, 2019)

FcRγ deficiency improves survival in experimental sepsis by down-regulating TLR4 signaling pathway - Zhi-Min Wei; Zhuo Wang; Xiao-Jian Wan; Xian-Jing Li; Yi-Xing Li; Yang Bai; Xue Yang; Yong Yang; Shun-Chang Jiao; Zhe-Feng Liu (Immunologic Research, 2019)

LaMIR166a-mediated auxin biosynthesis and signalling affect somatic embryogenesis in Larix leptolepis - Zhe-Xin Li; Yan-Ru Fan; Shao-Fei Dang; Wan-Feng Li; Li-Wang Qi; Su-ying Han (Molecular Genetics and Genomics, 2018)

A half-type ABC transporter FeSTAR1 regulates Al resistance possibly via UDP-glucose-based hemicellulose metabolism and Al binding - Jia Meng Xu; He Qiang Lou; Jian Feng Jin; Wei Wei Chen; Jiang Xue Wan; Wei Fan; Jian Li Yang (Plant and Soil, 2018)

Effects of soil improvement technology on soil quality in solar greenhouse - Wan-li Xiao; Zhe-xin Wang; Feng-zhi Wu; Xin-gang Zhou (Environmental Science and Pollution Research, 2018)

Alterations in Normal Aging Revealed by Cortical Brain Network Constructed Using IBASPM - Wan Li; Chunlan Yang; Feng Shi; Qun Wang; Shuicai Wu; Wangsheng Lu; Shaowu Li; Yingnan Nie; Xin Zhang (Brain Topography, 2018)

Risk factors, outcomes and genotypes of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream infection: a three-year retrospective study in a large tertiary hospital in Northern China - Si-Han Zheng; Sheng-Ji Cao; Hui Xu; Dan Feng; Li-Ping Wan; Guang-Jie Wang; Xiao-Guang Xiao (Infectious Diseases, 2018)

ELMOD3, a novel causative gene, associated with human autosomal dominant nonsyndromic and progressive hearing loss - Wu Li; Jie Sun; Jie Ling; Jiada Li; Chufeng He; Yalan Liu; Hongsheng Chen; Meichao Men; Zhijie Niu; Yuyuan Deng; Meng Li; Taoxi Li; et al. (Human Genetics, 2018)

Analysis of physiological and miRNA responses to Pi deficiency in alfalfa (Medicago sativa L.) - Zhenyi Li; Hongyu Xu; Yue Li; Xiufu Wan; Zhao Ma; Jing Cao; Zhensong Li; Feng He; Yufei Wang; Liqiang Wan; Zongyong Tong; Xianglin Li (Plant Molecular Biology, 2018)

Interaction network of core ABA signaling components in maize - Ying-Ge Wang; Feng-Ling Fu; Hao-Qiang Yu; Tao Hu; Yuan-Yuan Zhang; Yi Tao; Jian-Kang Zhu; Yang Zhao; Wan-Chen Li (Plant Molecular Biology, 2018)

The complete chloroplast genome sequence of Dodonaea viscosa: comparative and phylogenetic analyses - Josphat K. Saina; Andrew W. Gichira; Zhi-Zhong Li; Guang-Wan Hu; Qing-Feng Wang; Kuo Liao (Genetica, 2018)

MIR166a Affects the Germination of Somatic Embryos in Larixleptolepis by Modulating IAA Biosynthesis and Signaling Genes - Zhe-Xin Li; Li-Feng Zhang; Wan-Feng Li; Li-Wang Qi; Su-Ying Han (Journal of Plant Growth Regulation, 2017)

ABA pretreatment enhances the chilling tolerance of a chilling-sensitive rice cultivar - Xiang Hongtao; Wang Tongtong; Zheng Dianfeng; Wang Lizhi; Feng Yanjiang; Luo Yu; Li Rui; Li Zhongjie; Meng Ying; Li Wan; Wang Lianmin; Yang Chunjie (Brazilian Journal of Botany, 2017)

Establishment of a somatic embryo regeneration system and expression analysis of somatic embryogenesis-related genes in Chinese chestnut (Castanea mollissima Blume) - Dan Lu; Wei Wei; Wan Zhou; Linda D. McGuigan; Fei-yang Ji; Xiao Li; Yu Xing; Qing Zhang; Ke-feng Fang; Qing-qin Cao; Ling Qin (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Demographic history and population genetic structure of Hagenia abyssinica (Rosaceae), a tropical tree endemic to the Ethiopian highlands and eastern African mountains - Andrew W. Gichira; Zhi-Zhong Li; Josphat K. Saina; Guang-Wan Hu; Robert W. Gituru; Qing-Feng Wang; Jin-Ming Chen (Tree Genetics & Genomes, 2017)

Quantification of mycotoxins in vegetable oil by UPLC-MS/MS after magnetic solid-phase extraction - Yan Zhao; Li-Hong Wan; Xiao-Lin Bai; Yi-Ming Liu; Feng-Ping Zhang; Yao-Min Liu; Xun Liao (Food Additives & Contaminants: Part A, 2017)

The function of OsbHLH068 is partially redundant with its homolog, AtbHLH112, in the regulation of the salt stress response but has opposite functions to control flowering in Arabidopsis - Hung-Chi Chen; Vicki Hsieh-Feng; Pei-Chun Liao; Wan-Hsing Cheng; Li-Yu Liu; Yun-Wei Yang; Ming-Hsin Lai; Men-Chi Chang (Plant Molecular Biology, 2017)

The K+/H+ antiporter AhNHX1 improved tobacco tolerance to NaCl stress by enhancing K+ retention - Wei-Wei Zhang; Jing-Jing Meng; Jin-Yi Xing; Sha Yang; Feng Guo; Xin-Guo Li; Shu-Bo Wan (Journal of Plant Biology, 2017)

Anti-proliferative effects of paeonol on human prostate cancer cell lines DU145 and PC-3 - Yi Xu; Jian-yong Zhu; Zhang-ming Lei; Li-jun Wan; Xiu-wen Zhu; Feng Ye; Yan-yue Tong (Journal of Physiology and Biochemistry, 2017)

Laboratory study on cement admixed marine silt bricks - Yu-Feng Gao; Li-Ya Wang; Yu-Kuai Wan; Bing Li; Jia He (Marine Georesources & Geotechnology, 2017)

Transcriptome analysis provides insights into wood formation during larch tree aging - Wan-Feng Li; Wen-Hua Yang; Shou-Gong Zhang; Su-Ying Han; Li-Wang Qi (Tree Genetics & Genomes, 2017)

Young Seedling Stripe1 encodes a chloroplast nucleoid-associated protein required for chloroplast development in rice seedlings - Kunneng Zhou; Yulong Ren; Feng Zhou; Ying Wang; Long Zhang; Jia Lyu; Yihua Wang; Shaolu Zhao; Weiwei Ma; Huan Zhang; Liwei Wang; Chunming Wang; et al. (Planta, 2017)

Geochemistry of fine-grained clastic rocks in the Mesoproterozoic Kawabulake Group: implications for provenance and the tectonic model of the Eastern Tianshan, Xinjiang, NW China - Deng-Feng Li; Hua-Yong Chen; Li Zhang; Philip Fralick; Pete Hollings; Mei Mi; Wan-Jian Lu; Jin-Sheng Han; Cheng-Ming Wang; Jing Fang (International Journal of Earth Sciences, 2017)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Parallel viewshed analysis on a PC cluster system using triple-based irregular partition scheme - Xiao-Dong Song; Guo-An Tang; Xue-Jun Liu; Wan-Feng Dou; Fa-Yuan Li (Earth Science Informatics, 2016)

Elevated Neurosteroids in the Lateral Thalamus Relieve Neuropathic Pain in Rats with Spared Nerve Injury - Meng Zhang; Jia Liu; Meng-Meng Zhou; Honghai Wu; Yanning Hou; Yun-Feng Li; Yuxin Yin; Lemin Zheng; Feng-Yu Liu; Ming Yi; You Wan (Neuroscience Bulletin, 2016)

Glacier change in the western Nyainqentanglha Range, Tibetan Plateau using historical maps and Landsat imagery: 1970-2014 - Kun-peng Wu; Shi-yin Liu; Wan-qin Guo; Jun-feng Wei; Jun-li Xu; Wei-jia Bao; Xiao-jun Yao (Journal of Mountain Science, 2016)

The occurrence and fate of siloxanes in wastewater treatment plant in Harbin, China - Bo Li; Wen-Long Li; Shao-Jing Sun; Hong Qi; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Ning-Zheng Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2016)

Effects of litter, seed position, and water availability on establishment of seedlings for two semiarid grass species - Guixia Liu; Liqiang Wan; Feng He; Zongyong Tong; Zhongkuan Liu; Xianglin Li (Plant Ecology, 2016)

Feasibility of an enhanced washing process to extract PBDEs/heavy metals/antibiotics from antibiotic resistance gene-affected soil with aqueous DNA followed by microbial augmentation - Mao Ye; Mingming Sun; Jinzhong Wan; Yu Zhao; Shanni Xie; Da Tian; Feng Hu; Huixin Li; Lianggang Zong; Fredrick Orori Kengara; Jiang Xin (Journal of Soils and Sediments, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Glacier changes since the early 1960s, eastern Pamir, China - Zhen Zhang; Jun-li Xu; Shi-yin Liu; Wan-qin Guo; Jun-feng Wei; Tong Feng (Journal of Mountain Science, 2016)

Overexpression of a phospholipase Dα gene from Ammopiptanthus nanus enhances salt tolerance of phospholipase Dα1-deficient Arabidopsis mutant - Hao Qiang Yu; Tai Ming Yong; Hong Jie Li; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Planta, 2015)

Repair of articular cartilage defects in rabbits through tissue-engineered cartilage constructed with chitosan hydrogel and chondrocytes - Ming Zhao; Zhu Chen; Kang Liu; Yu-qing Wan; Xu-dong Li; Xu-wei Luo; Yi-guang Bai; Ze-long Yang; Gang Feng (Journal of Zhejiang University-SCIENCE B, 2015)

Peanut violaxanthin de-epoxidase alleviates the sensitivity of PSII photoinhibition to heat and high irradiance stress in transgenic tobacco - Sha Yang; De-Yun Meng; Lin-Lin Hou; Yan Li; Feng Guo; Jing-Jing Meng; Shu-Bo Wan; Xin-Guo Li (Plant Cell Reports, 2015)

Cloning and functional validation of molybdenum cofactor sulfurase gene from Ammopiptanthus nanus - Hao Qiang Yu; Yuan Yuan Zhang; Tai Ming Yong; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Plant Cell Reports, 2015)

Mass loss from glaciers in the Chinese Altai Mountains between 1959 and 2008 revealed based on historical maps, SRTM, and ASTER images - Jun-feng Wei; Shi-yin Liu; Jun-li Xu; Wan-qin Guo; Wei-jia Bao; Dong-hui Shangguan; Zong-li Jiang (Journal of Mountain Science, 2015)

Numerical and experimental study on the performance of flat-plate photobioreactors with different inner structures for microalgae cultivation - Jianke Huang; Shaofeng Kang; Minxi Wan; Yuanguang Li; Xiaoxing Qu; Fei Feng; Jun Wang; Weiliang Wang; Guomin Shen; Wei Li (Journal of Applied Phycology, 2015)

Enhanced soil washing process for the remediation of PBDEs/Pb/Cd-contaminated electronic waste site with carboxymethyl chitosan in a sunflower oil–water solvent system and microbial augmentation - Mao Ye; Mingming Sun; Jinzhong Wan; Guodong Fang; Huixin Li; Feng Hu; Xin Jiang; Fredrick Orori Kengara (Environmental Science and Pollution Research, 2015)

Experimental Study on the Effect of Electrostimulation on Neural Regeneration After Oculomotor Nerve Injury - Ningxi Zhu; Chunmei Zhang; Zhen Li; Youqiang Meng; Baohui Feng; Xuhui Wang; Min Yang; Liang Wan; Bo Ning; Shiting Li (Journal of Molecular Neuroscience, 2014)

Expression Profile of Maize MicroRNAs Corresponding to Their Target Genes Under Drought Stress - Ying-Ge Wang; Ming An; Shu-Feng Zhou; Yue-Hui She; Wan-Chen Li; Feng-Ling Fu (Biochemical Genetics, 2014)

Erratum to: Overexpression of Human E46K Mutant α-Synuclein Impairs Macroautophagy via Inactivation of JNK1-Bcl-2 Pathway - Jia-Qing Yan; Yu-He Yuan; Yan-Na Gao; Ju-Yang Huang; Kai-Li Ma; Yan Gao; Wan-Qing Zhang; Xiao-Feng Guo; Nai-Hong Chen (Molecular Neurobiology, 2014)

Overexpression of Human E46K Mutant α-Synuclein Impairs Macroautophagy via Inactivation of JNK1-Bcl-2 Pathway - Jia-Qing Yan; Yu-He Yuan; Yan-Na Gao; Ju-Yang Huang; Kai-Li Ma; Yan Gao; Wan-Qing Zhang; Xiao-Feng Guo; Nai-Hong Chen (Molecular Neurobiology, 2014)

A comparative analysis of endophytic bacterial communities associated with hyperaccumulators growing in mine soils - Liang Chen; Shenglian Luo; Jueliang Chen; Yong Wan; Xiaojie Li; Chengbin Liu; Feng Liu (Environmental Science and Pollution Research, 2014)

Cloning and characterization of four differentially expressed cDNAs encoding NFYA homologs involved in responses to ABA during somatic embryogenesis in Japanese larch (Larix leptolepis) - Li-feng Zhang; Wan-feng Li; Hai-yan Xu; Li-wang Qi; Su-ying Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

EPO-Dependent Activation of PI3K/Akt/FoxO3a Signalling Mediates Neuroprotection in In Vitro and In Vivo Models of Parkinson’s Disease - Yu Jia; Shi-Jing Mo; Qi-Qi Feng; Ma-Li Zhan; Li-Si OuYang; Jia-Chang Chen; Yu-Xin Ma; Jia-Jia Wu; Wan-Long Lei (Journal of Molecular Neuroscience, 2014)

Regulation of synchronism by abscisic-acid-responsive small noncoding RNAs during somatic embryogenesis in larch (Larix leptolepis) - Jun-Hong Zhang; Shou-Gong Zhang; Shui-Gen Li; Su-Ying Han; Wan-Feng Li; Xin-Min Li; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

The post-transcriptional regulation of LaSCL6 by miR171 during maintenance of embryogenic potential in Larix kaempferi (Lamb.) Carr. - Wan-Feng Li; Shou-Gong Zhang; Su-Ying Han; Tao Wu; Jun-Hong Zhang; Li-Wang Qi (Tree Genetics & Genomes, 2014)

Three new olean-type triterpenoid saponins from aerial parts of Eclipta prostrata (L.) - Feng-Min Xi; Chun-Tong Li; Jun-Ling Mi; Zhi-Jun Wu; Wan-Sheng Chen (Natural Product Research, 2014)

Concentration, Sources and Human Exposure of Polybrominated Diphenyl Ethers in Indoor Dust in Heilongjiang Province, China - Ning-zheng Zhu; Hong Qi; Feng Zhang; Wan-li Ma; Li-yan Liu; Yi-fan Li (Bulletin of Environmental Contamination and Toxicology, 2013)

Oculomotor Nerve Injury Induces Nuerogenesis in the Oculomotor and Edinger–Westphal Nucleus of Adult Dog - Ningxi Zhu; Chunmei Zhang; Zhen Li; Youqiang Meng; Baohui Feng; Xuhui Wang; Min Yang; Liang Wan; Bo Ning; Shiting Li (Journal of Molecular Neuroscience, 2013)

Polycyclic aromatic hydrocarbons in water, sediment and soil of the Songhua River Basin, China - Wan-Li Ma; Li-Yan Liu; Hong Qi; Zi-Feng Zhang; Wei-Wei Song; Ji-Min Shen; Zhong-Lin Chen; Nan-Qi Ren; Josey Grabuski; Yi-Fan Li (Environmental Monitoring and Assessment, 2013)

Better environmental data may reverse conclusions about niche‐ and dispersal‐based processes in community assembly - Li-Wan Chang; David Zelený; Ching-Feng Li; Shau-Ting Chiu; Chang-Fu Hsieh (Ecology, 2013)
Variation partitioning of species composition into components explained by environmental and spatial variables is often used to identify a signature of niche‐ and dispersal‐based processes in community assembly. Such interpretation, however, strongly depends on the quality of the environmental data available. In recent studies conducted in forest dynamics plots, the environment was represented only by readily available topographical variables. Using data from a subtropical broad‐leaved dynamics plot in Taiwan, we focus on the question of how would the conclusion about importance of niche‐ and dispersal‐based processes change if soil variables are also included in the analysis. To gain further insight, we introduced multiscale decomposition of a pure spatial component [c] in variation partitioning. Our results indicate that, if only topography is included, dispersal‐based processes prevail, while including soil variables reverses this conclusion in favor of niche‐based processes. Multiscale decomposition of [c] shows that if only topography was included, broad‐scaled spatial variation prevails in [c], indicating that other as yet unmeasured environmental variables can be important. However, after also including soil variables this pattern disappears, increasing importance of meso‐ and fine‐scaled spatial patterns indicative of dispersal processes.

qLTG-9, a stable quantitative trait locus for low-temperature germination in rice (Oryza sativa L.) - Linfang Li; Xi Liu; Kun Xie; Yihua Wang; Feng Liu; Qiuyun Lin; Wenyan Wang; Chunyan Yang; Bingyue Lu; Shijia Liu; Liangming Chen; Ling Jiang; et al. (Theoretical and Applied Genetics, 2013)

RNA interference-mediated resistance to maize dwarf mosaic virus - Zhi-Yong Zhang; Ying-Ge Wang; Xiao-Juan Shen; Lei Li; Shu-Feng Zhou; Wan-Chen Li; Feng-Ling Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Detection of African swine fever virus-like sequences in ponds in the Mississippi Delta through metagenomic sequencing - Xiu-Feng Wan; J. Lamar Barnett; Fred Cunningham; Si Chen; Guohua Yang; Shannon Nash; Li-Ping Long; Lorelei Ford; Sherry Blackmon; Yan Zhang; Larry Hanson; Qiang He (Virus Genes, 2013)

Cambium reactivation independent of bud unfolding involves de novo IAA biosynthesis in cambium regions in Populus tomentosa Carr. - Wan-Feng Li; Qi Ding; Ke-Ming Cui; Xin-Qiang He (Acta Physiologiae Plantarum, 2013)

Regulation of LaMYB33 by miR159 during maintenance of embryogenic potential and somatic embryo maturation in Larix kaempferi (Lamb.) Carr. - Wan-Feng Li; Shou-Gong Zhang; Su-Ying Han; Tao Wu; Jun-Hong Zhang; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Pathology of urethral fibromuscular system related to parturition-induced stress urinary incontinence and TGF-β1/Smad pathway - Guang-Yong Li; Wan-Shou Cui; Feng Zhou; Zhe-Zhu Gao; Hua Xin; Tao Liu; Wei-Ren Li; Yan-Qing Gong; Guang-Yi Bai; Ying-Lu Guo; Zhong-Cheng Xin (Molecular and Cellular Biochemistry, 2012)

Formaldehyde up-regulates TRPV1 through MAPK and PI3K signaling pathways in a rat model of bone cancer pain - Ying Han; Yan Li; Xing Xiao; Jia Liu; Xiang-Ling Meng; Feng-Yu Liu; Guo-Gang Xing; You Wan (Neuroscience Bulletin, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

N and O isotopes and the ore-forming mechanism of nitrate deposits in the Turpan-Hami Basin, Xinjiang, China - Yan Qin; YanHe Li; Feng Liu; KeJun Hou; DeFang Wan; Cheng Zhang (Science China Earth Sciences, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Type 17 T-helper cells might be a promising therapeutic target for osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Yi-Qing Zhao; Cheng-Wan Li; Jian-Ping Li; Jun-Ming Sun; Rui-Sheng Xu (Molecular Biology Reports, 2012)

Suboptimal Selenium Supply—A Continuing Problem in Keshan Disease Areas in Heilongjiang Province - Jie Hou; Tong Wang; Mingfa Liu; Shaochen Li; Jie Chen; Chunxu Liu; Hui Zhang; Yiru Wang; Zengchao Liu; Na Liang; Yuezhu Wan; Qi Li; et al. (Biological Trace Element Research, 2011)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Age-related changes in the anatomical characteristics of Peyer's patches in small intestine of Bactrian camels (Camelus bactrianus) - Shan-Shan Qi; Wen-Hui Wang; Qiang Gao; Xiao-Hong Xu; Wan-Hong He; Ying-Pai Zhaxi; Li-Feng Tai (Tropical Animal Health and Production, 2011)

Targeting interleukin-21 in rheumatoid arthritis - Feng-Lai Yuan; Wei Hu; Wei-Guo Lu; Xia Li; Jian-Ping Li; Rui-Sheng Xu; Cheng-Wan Li; Fei-Hu Chen; Cheng Jin (Molecular Biology Reports, 2011)

Effect of host plants on development and reproduction of Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) - Rui-Ting Ju; Feng Wang; Fang-Hao Wan; Bo Li (Journal of Pest Science, 2011)

A young and booming approach: the extreme lateral supracerebellar infratentorial approach - Xin Chen; Yu-Gong Feng; Wan-Zhong Tang; Huan-Ting Li; Zhao-Jian Li (Neuroscience Bulletin, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

The vacuolar ATPase in bone cells: a potential therapeutic target in osteoporosis - Feng-Lai Yuan; Xia Li; Wei-Guo Lu; Cheng-Wan Li; Jian-Ping Li; Yu Wang (Molecular Biology Reports, 2010)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

The application of fuzzy risk in researching flood disasters - Li-Hua Feng; Wei-Hu Hong; Zi Wan (Natural Hazards, 2010)

Geographic substructure of Fusarium asiaticum isolates collected from barley in China - Zheng Zhang; Hao Zhang; Theo van der Lee; Wan-Quan Chen; Paul Arens; Jin Xu; Jing-Sheng Xu; Li-Jun Yang; Da-Zhao Yu; Cees Waalwijk; Jie Feng (European Journal of Plant Pathology, 2010)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

Cloning and Characterization of Functional Trehalose-6-Phosphate Synthase Gene in Maize - Wei Jiang; Feng-Ling Fu; Su-Zhi Zhang; Ling Wu; Wan-Chen Li (Journal of Plant Biology, 2010)

A novel polymorphism of GDF5 gene and its association with body measurement traits in Bos taurus and Bos indicus breeds - Yong Feng Liu; Lin Sen Zan; Kui Li; Shuan Ping Zhao; Ya Ping Xin; Qing Lin; Wan Qiang Tian; Zhi Wei Wang (Molecular Biology Reports, 2010)

Circulating B7-H3(CD276) Elevations in Cerebrospinal Fluid and Plasma of Children with Bacterial Meningitis - Xuqin Chen; Guangbo Zhang; Yan Li; Xing Feng; Fengguo Wan; Liya Zhang; Jian Wang; Xueguang Zhang (Journal of Molecular Neuroscience, 2009)

Isolation and characterization of microsatellite markers for Primulina tabacum, a critically endangered perennial herb - Zheng-Feng Wang; Hai Ren; Qian-Mei Zhang; Wan-Hui Ye; Kai-Ming Liang; Zhong-Chao Li (Conservation Genetics, 2009)

Reduction in SBPase Activity by Antisense RNA in Transgenic Rice Plants: Effect on Photosynthesis, Growth, and Biomass Allocation at Different Nitrogen Levels - Lingling Feng; Hui Li; Jingmei Jiao; Ding Li; Li Zhou; Jian Wan; Yangsheng Li (Journal of Plant Biology, 2009)

Isolation and characterization of microsatellite markers for Cycas hainanensis C. J. Chen (Cycadaceae) - Min Zhang; Zheng-Feng Wang; Shu-Guang Jian; Wan-Hui Ye; Hong-Lin Cao; Peng Zhu; Ling Li (Conservation Genetics, 2009)

Isolation and characterization of ten polymorphic microsatellite in the endangered tree Erythrophleum fordii oliv - Peng Zhu; Wan-Hui Ye; Zheng-Feng Wang; Hong-Lin Cao; Min Zhang; Ling Li; Wei Xiao (Conservation Genetics, 2009)

Isolation and characterization of microsatellite loci in endangered Cycas changjiangensis (Cycadaceae) - Ling Li; Zheng-Feng Wang; Shu-Guang Jian; Peng Zhu; Min Zhang; Wan-Hui Ye; Hai Ren (Conservation Genetics, 2009)

Quantification of silkworm coactivator of MBF1 mRNA by SYBR Green I real-time RT-PCR reveals tissue- and stage-specific transcription levels - Guang-li Li; Bhaskar Roy; Xing-hua Li; Wan-fu Yue; Xiao-feng Wu; Jian-mei Liu; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Differential Expression of Serine/Threonine Protein Phosphatase Type-2C Under Drought Stress in Maize - Fu-Hua Li; Feng-Ling Fu; Li-Na Sha; Liang He; Wan-Chen Li (Plant Molecular Biology Reporter, 2009)

High-level expression of orange fluorescent protein in the silkworm larvae by the Bac-to-Bac system - Jian-mei Liu; Wan Chi Cheong David; Denis Tsz-Ming Ip; Xing-hua Li; Guang-li Li; Xiao-feng Wu; Wan-fu Yue; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Identification and characterization of a new coleviroid (CbVd-5) - Wan-Ying Hou; Teruo Sano; Feng Li; Zu-Jian Wu; Li Li; Shi-Fang Li (Archives of Virology, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Circulating B7-H3(CD276) Elevations in Cerebrospinal Fluid and Plasma of Children with Bacterial Meningitis - Xuqin Chen; Guangbo Zhang; Yan li; Xing Feng; Fengguo Wan; Liya Zhang; Jian Wang; Xueguang Zhang (Journal of Molecular Neuroscience, 2009)

Effects of silkworm larvae powder containing manganese superoxide dismutase on immune activity of mice - Wan-Fu Yue; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Jian-Tong Sun; Hong-Xiang Sun; Yun-Gen Miao (Molecular Biology Reports, 2008)

Availability and toxicity of Fe(II) and Fe(III) in Caco-2 cells - Wan-ling He; Ying Feng; Xiao-li Li; Yan-yan Wei; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Identification and characterization of EST-SSRs and cpSSRs in endangered Cycas hainanensis - Zheng-Feng Wang; Wan-Hui Ye; Hong-Lin Cao; Zhong-Chao Li; Shao-Lin Peng (Conservation Genetics, 2008)

Triassic Nb-enriched basalts, magnesian andesites, and adakites of the Qiangtang terrane (Central Tibet): evidence for metasomatism by slab-derived melts in the mantle wedge - Qiang Wang; Derek A. Wyman; Jifeng Xu; Yusheng Wan; Chaofeng Li; Feng Zi; Ziqi Jiang; Huaning Qiu; Zhuyin Chu; Zhenhua Zhao; Yanhui Dong (Contributions to Mineralogy and Petrology, 2008)

Human tau protein forms complex with PrP and some GSS- and fCJD-related PrP mutants possess stronger binding activities with tau in vitro - Xiao-Fan Wang; Chen-Fang Dong; Jin Zhang; Yan-Zhen Wan; Feng Li; Yin-Xia Huang; Lu Han; Bing Shan; Chen Gao; Jun Han; Xiao-Ping Dong (Molecular and Cellular Biochemistry, 2008)

Characterizing and estimating rice brown spot disease severity using stepwise regression, principal component regression and partial least-square regression - Zhan-yu Liu; Jing-feng Huang; Jing-jing Shi; Rong-xiang Tao; Wan Zhou; Li-li Zhang (Journal of Zhejiang University-SCIENCE B, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Antitumor activities of D-glucosamine and its derivatives - Li Zhang; Wan-shun Liu; Bao-qin Han; Yan-fei Peng; Dong-feng Wang (Journal of Zhejiang University-SCIENCE B, 2006)

Mineralogical and geochemical study of a newly discovered mafic granulite, northwest China: Implications for tectonic evolution of the Altay Orogenic Belt - Han‐Lin Chen; Zi‐Long Li; Shu‐Feng Yang; Chuan‐Wan Dong; Wen‐Jiao Xiao; Yoshiaki Tainosho (Island Arc, 2006)
A mafic granulite body was newly discovered in the Altay Orogenic Belt, northwest China. The rocks comprise a suite of coarse‐grained and fine‐grained granulites. Orthopyroxenes (hypersthenes) in the rocks have high X Mg and low Al 2 O 3 contents, whereas clinopyroxenes have low TiO 2 and Al 2 O 3 contents. Amphiboles and biotites have a high Mg/(Mg + Fe 2+ ) ratio and low contents of F and Cl. The peak metamorphic pressure–temperature (P–T) conditions are estimated as 750–780°C and 6–7 kbar, and retrograde P–T conditions are in the range of 590–620°C and 2.3–3.7 kbar, indicating significant decompression. Metamorphic reactions and P–T estimates define a clockwise P–T path. Geochemically, the rocks are high in Mg/(Mg + Fe) and Al 2 O 3 , depleted in U, Th, K and Rb, and characterized by light rare earth element enrichment and a weak positive Eu anomaly. The Altay mafic granulite shows depleted Nb, P and Ti contents in the mid‐oceanic ridge basalt normalized spider diagram. The geochemical characteristics suggest that the protolith of the Altay mafic granulite was calc‐alkaline basalt and andesite with an island‐arc affinity. The rock has a high 143 Nd/ 144 Nd ratio with ɛNd(0) > 0, indicating derivation from a mantle‐depleted source. In the present study, a two‐stage model for the evolution of the Altay mafic granulite is proposed: an early stage in which calc‐alkaline basalt and andesite with island‐arc affinity were subducted into a deeper level of the crust and subjected to granulite‐facies metamorphism generating the mafic granulite, followed by the later stage exhumation of the system into the upper crust by the late Paleozoic thrusting.

Identification of the Binding Domain of Signal-Transduction-Related Proteins on c-Mpl - Limin Yang; Libing Feng; Li Huang; Weiguo Zhou; Min Wan; Shouyuan Zhao; Changben Li (Biochemical Genetics, 2003)